Resin composition and method for manufacturing element using same

The resin composition addresses uneven film thickness and leakage current issues by using polymers bonded and unbonded to inorganic particles with hydrogen bonding, enhancing film uniformity and reducing leakage current for improved electronic device performance.

JP7600562B2Active Publication Date: 2024-12-17TORAY INDUSTRIES INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020140659
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-27
Filing Date
2020-08-24
Publication Date
2024-12-17
Estimated Expiration
2040-08-24

AI Technical Summary

Technical Problem

Existing resin compositions for insulating films in electronic devices, such as field-effect transistors (FETs) and capacitors, suffer from uneven film thickness and increased leakage current, particularly in capacitors with large lower electrodes, due to the low fluidity of polymers bonded to inorganic particles, leading to conductive paths and variations in device characteristics.

Method used

A resin composition comprising polymers bonded and unbonded to inorganic particles, with specific functional groups for hydrogen bonding, and a solvent, which enhances film uniformity and reduces leakage current by improving fluidity and suppressing particle aggregation.

Benefits of technology

The composition achieves high dielectric constant and low leakage current, resulting in uniform insulating films with improved device performance and reduced variations in characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600562000018
    Figure 0007600562000018
  • Figure 0007600562000019
    Figure 0007600562000019
  • Figure 0007600562000020
    Figure 0007600562000020
Patent Text Reader

Abstract

To provide a resin composition that can form an insulating layer with high dielectric constants and reduced leakage currents.SOLUTION: A resin composition at least has (a) polymer A: a polymer in which a polymer is bound to an inorganic particle having a hydroxy group on the surface, (b) polymer B: a polymer that is not bound to an inorganic particle and has a functional group capable of forming a hydrogen bond with a hydroxy group on the inorganic particle in the polymer A, and (C) a solvent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a method for producing an element using the same. [Background technology]

[0002] In recent years, technologies that use coating methods to manufacture electronic devices such as electronic paper, flexible sensors, and RFID (Radio Frequency IDentification) tags have been investigated. Coating methods can be used to avoid vacuum and high-temperature processes, making it possible to manufacture electronic devices at low cost.

[0003] Electronic devices include elements such as field-effect transistors (FETs) and capacitors. These elements require an insulating film to insulate the upper and lower electrodes.

[0004] The insulating film in a FET is the gate insulating film that separates the semiconductor layer, source electrode, drain electrode, and gate electrode. The electrical characteristics, surface smoothness, and film thickness of the gate insulating film have a significant effect on FET characteristics such as leakage current value and FET ON / OFF current value.

[0005] The insulating film in a capacitor is a dielectric film that separates the upper and lower electrodes and stores the electric charge generated by the electric field applied between the upper and lower electrodes. The electrical characteristics, surface smoothness, and film thickness of the dielectric film have a significant effect on the capacitor characteristics such as the leakage current value and the amount of stored charge.

[0006] As materials for insulating films, organic materials that are soluble in organic solvents, such as organic polymers, are being actively studied. These materials can be formed into thin films at low cost using coating methods such as slit coating, and can be formed into thin films on film substrates such as polyethylene terephthalate using low-temperature processes. In particular, the addition of inorganic compounds to insulating films has been actively studied in order to increase the dielectric constant of the insulating film.

[0007] Known examples of insulating films in which an inorganic compound is added to an organic polymer include a gate insulating film containing polysiloxane chemically bonded to inorganic particles (see, for example, Patent Document 1) and a gate insulating film containing a polymer and inorganic oxide particles (see, for example, Patent Document 2). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] International Publication No. 2019 / 065561 [Patent Document 2] JP 2013-115162 A Summary of the Invention [Problem to be solved by the invention]

[0009] However, it has become clear that the technology described in Patent Document 1 has a problem in that the thickness of the insulating film becomes uneven near the lower electrode, causing an increase in leakage current of the element. Furthermore, Patent Document 1 does not mention capacitors, and it has been found that the above problem is particularly prominent in capacitors with a large lower electrode area.

[0010] Furthermore, the inventors of the present invention have studied the technology of Patent Document 2 and have found that although there is little unevenness in the thickness of the insulating film, the formation of conductive paths by some of the aggregated inorganic particles results in an increase in the leakage current of the capacitor.

[0011] The present invention has been made in view of the above problems, and has an object to provide a resin composition capable of forming an insulating layer having a high dielectric constant and reduced leakage current. [Means for solving the problem]

[0012] The present inventors hypothesized that the cause of the unevenness in film thickness near the electrode in the technology of Patent Document 1 was the low fluidity of the polymer chemically bonded to the inorganic particles, and conducted research, leading to the present invention.

[0013] That is, the present invention is a resin composition containing at least (a) polymer A: a polymer bonded to inorganic particles having hydroxyl groups on the surface thereof, (b) polymer B: a polymer that is not bonded to inorganic particles and has functional groups capable of forming hydrogen bonds with hydroxyl groups on the surface of the inorganic particles contained in polymer A, and (c) a solvent. Effect of the Invention

[0014] According to the element of the present invention, a resin composition capable of forming an insulating film with high uniformity in film thickness near and on an electrode can be obtained, and as a result, an element can be obtained in which the insulating film has both a high dielectric constant and a low leakage current. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a field-effect transistor obtained using the resin composition of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view showing an example of a field-effect transistor obtained using the resin composition of the present invention. [Diagram 3] FIG. 1 is a schematic cross-sectional view showing an example of a field-effect transistor obtained using the resin composition of the present invention. [Figure 4] FIG. 1 is a schematic cross-sectional view showing an example of a field-effect transistor obtained using the resin composition of the present invention. [Diagram 5] FIG. 1 is a schematic cross-sectional view showing an example of a field-effect transistor obtained using the resin composition of the present invention. [Figure 6] FIG. 1 is a schematic cross-sectional view showing an example of a field-effect transistor obtained using the resin composition of the present invention. [Figure 7] FIG. 1 is a schematic cross-sectional view showing an example of a capacitor obtained using a resin composition of the present invention. [Figure 8] FIG. 1 is a schematic cross-sectional view showing an example of a capacitor obtained using a resin composition of the present invention. [Figure 9] FIG. 1 is a schematic cross-sectional view showing an example of a capacitor obtained using a resin composition of the present invention. [Figure 10]FIG. 1 is a schematic cross-sectional view showing an example of a capacitor obtained using a resin composition of the present invention. [Figure 11] FIG. 1 is a schematic cross-sectional view showing an example of a circuit obtained using the resin composition of the present invention. [Figure 12] FIG. 1 is a schematic cross-sectional view showing an example of a circuit obtained using the resin composition of the present invention. [Figure 13] FIG. 1 is a schematic cross-sectional view showing an example of a circuit obtained using the resin composition of the present invention. [Figure 14] FIG. 1 is a block diagram showing an example of a wireless communication device using a field effect transistor obtained using the resin composition of the present invention. [Figure 15] FIG. 1 is a schematic cross-sectional view showing an example of a capacitor obtained using a resin composition of the present invention. [Figure 16] FIG. 1 is a schematic cross-sectional view showing an example of a field-effect transistor obtained using the resin composition of the present invention. [Figure 17] FIG. 1 is a schematic cross-sectional view showing an example of a circuit obtained using the resin composition of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, preferred embodiments of the resin composition according to the present invention and the method for manufacturing an element using the same will be described in detail. However, the present invention is not limited to the following embodiments, and can be modified in various ways depending on the purpose and application.

[0017] <Resin composition> The resin composition of the present invention is a resin composition containing at least (a) polymer A: a polymer bonded to inorganic particles having hydroxyl groups on the surface thereof, (b) polymer B: a polymer that is not bonded to inorganic particles and has functional groups capable of forming hydrogen bonds with hydroxyl groups on the surface of the inorganic particles contained in polymer A, and (c) a solvent.

[0018] (Polymer A: a polymer to which inorganic particles having hydroxyl groups on the surface are bonded) The "bond" in the "polymer having inorganic particles bonded thereto" is a bond selected from the group consisting of covalent bonds, ionic bonds, coordinate bonds, metallic bonds, hydrogen bonds, bonds based on pi-pi interactions, bonds based on ion-dipole interactions, bonds based on dipole-dipole interactions, bonds based on dipole-induced dipole interactions, bonds based on hydrophobic interactions, bonds based on charge transfer complex formation, bonds based on metal-ligand complex formation, bonds based on London dispersion forces, and bonds based on van der Waals forces.

[0019] The inorganic particles have functional groups such as hydroxyl groups on their surfaces that can react with polymers, and the inorganic particles react with the polymers at these functional groups, and the inorganic particles are incorporated into the polymers. When the inorganic particles are bonded to the polymer, the aggregation of the inorganic particles in a solution state is suppressed compared to when the inorganic particles are mixed with the polymer. Furthermore, when the inorganic particles are bonded to the polymer, the alkali solubility of the inorganic particles is improved, so that when the cured film obtained from the resin composition of the present invention (hereinafter, unless otherwise specified, the term "cured film" simply refers to the cured film obtained from the resin composition of the present invention) is developed in an alkali state, the deterioration of pattern processability due to the generation of residues can be suppressed. It is preferable that the "bond" is a covalent bond from the viewpoints of aggregation suppression and pattern processability.

[0020] The presence or absence of bonding between inorganic particles and polymers is 13 C-NMR, 29 It can be confirmed by combining analytical methods such as Si-NMR and IR. For example, 13 C-NMR or 29 Using Si-NMR, the spectrum of the inorganic particles, the spectrum of the polymer, and the spectrum of the polymer to which the inorganic particles are bonded are compared. The peaks derived from the C or Si atoms bonded to the inorganic particles in the polymer to which the inorganic particles are bonded are peaks with chemical shifts that do not exist in the spectrum of the polymer, so it is possible to confirm the presence or absence of bonding between the inorganic particles and the polymer.

[0021] Similarly, in IR, the peaks derived from C or Si atoms in a polymer to which inorganic particles are bonded have a different wavenumber from the spectrum of the polymer, making it possible to confirm whether or not the inorganic particles are bonded to the polymer.

[0022] (Inorganic particles) The inorganic particles are not particularly limited as long as they are particles made of an inorganic substance. Since the inorganic particles have a small shrinkage rate during thermal curing, they can suppress the generation of shrinkage stress. Therefore, the crack resistance of the cured film obtained from the resin composition of the present invention is improved, and the leakage current can be reduced.

[0023] As the inorganic particles, particles made of a metal compound or a semi-metal compound are preferred, and from the viewpoint of reactivity with the polymer, inorganic oxide particles are particularly preferred.

[0024] Examples of the metal or metalloid include elements selected from the group consisting of silicon, magnesium, calcium, strontium, barium, lanthanum, cerium, tin, titanium, zirconium, hafnium, yttrium, niobium, tantalum, and aluminum. Examples of the metal or metalloid compound include halides, oxides, nitrides, hydroxides, carbonates, sulfates, nitrates, or metasilicates of the above metals or metalloids.

[0025] There are no particular limitations on the shape of the inorganic particles, but in order to maintain a smooth surface of the cured film, a shape with a low aspect ratio is preferred, and a spherical shape is more preferred.

[0026] From the viewpoint of suppressing the aggregation of inorganic particles in a solution state and reducing leakage current by improving the crack resistance of the cured film, the number average particle diameter of the inorganic particles is preferably 1 nm or more, more preferably 5 nm or more, even more preferably 15 nm or more, and particularly preferably 20 nm or more.On the other hand, the number average particle diameter is preferably 100 nm or less, more preferably 70 nm or less, even more preferably 60 nm or less, and particularly preferably 50 nm or less.When the number average particle diameter is within the above range, the pattern processability of the cured film can be improved.

[0027] Here, the number average particle size of inorganic particles can be determined by the following measurement using a scanning electron microscope (SEM) or a transmission electron microscope (TEM). The cross section of the cured film is observed at a magnification of 50,000 to 200,000 times. If the inorganic particles are spherical, the diameter of the sphere is measured and used as the particle size of the particle. If the inorganic particles are not spherical, the longest diameter (hereinafter, "major axis diameter") and the longest diameter in a direction perpendicular to the major axis diameter (hereinafter, "minor axis diameter") are measured, and the biaxial average diameter obtained by averaging the major axis diameter and the minor axis diameter is used as the particle size of the particle. This particle size measurement is performed on 20 or more randomly selected particles, and the arithmetic average is used as the number average particle size.

[0028] Examples of inorganic particles used in the present invention include known particles such as those described in International Publication No. 2019 / 065561. Among them, from the viewpoint of increasing the dielectric constant of the cured film, inorganic particles selected from tin oxide-titanium oxide composite particles, silicon oxide-titanium oxide composite particles, titanium oxide particles, zirconium oxide particles, hafnium oxide particles, yttrium oxide particles, niobium oxide particles, tantalum oxide particles, tin oxide particles, tin oxide-zirconium oxide composite particles, silicon oxide-zirconium oxide composite particles, aluminum oxide particles, barium titanate particles, strontium titanate particles, barium titanate-strontium titanate composite particles, lead zirconate titanate particles, lanthanum lead zirconate titanate particles, strontium niobate bismuth particles, strontium niobate titanate bismuth particles, and strontium tantalate bismuth particles are more preferred, and from the viewpoint of availability, titanium oxide-containing particles such as tin oxide-titanium oxide composite particles, silicon oxide-titanium oxide composite particles, and titanium oxide particles are particularly preferred. By improving the dielectric constant of the cured film, the device characteristics of the device obtained by using the resin composition of the present invention are improved. For example, in the case of a FET, when the FET is driven (on) at a certain gate voltage value, the current flowing through the circuit increases.

[0029] (polymer) In the polymer A, the polymer is preferably soluble in a solvent. The polymer skeleton may be linear, cyclic, or branched. It is also preferable that a crosslinkable functional group, a polar functional group, or a functional group that controls various properties of the polymer is introduced into the side chain. By using a polymer with these controlled properties, for example, coatability, surface flatness, solvent resistance, transparency, and good wettability with other inks can be obtained in the process of producing an FET element. Furthermore, a good FET element with excellent durability and stability after the formation of the FET element can be obtained.

[0030] The polymer used in the present invention is not particularly limited as long as it exhibits an insulating property to the extent that the FET functions normally, and for example, polysiloxane, polyamide, polyamideimide, polyimide, polybenzimidazole, polyvinyl alcohol, polyvinylphenol, polyacetal, polycarbonate, polyarylate, polyphenylene sulfide, polyethersulfone, polyetherketone, polyphthalamide, polyethernitrile, polymethyl methacrylate, polymethacrylamide, polyvinylidene fluoride, polytetrafluoroethylene, polystyrene, polyester, aromatic polyether, novolac resin, phenol resin, acrylic resin, olefin resin, alicyclic olefin resin, vinyl chloride resin, epoxy resin, melamine resin, urea resin, etc. can be used. In addition, it is also possible to use a copolymer or mixture of these polymers with other polymers. Among these, polysiloxane is preferably used from the viewpoint of improving the on-current of the FET and reducing the leakage current.

[0031] The polysiloxane preferably has a structural unit represented by general formula (1).

[0032] [ka]

[0033] The polysiloxane having a structural unit represented by general formula (1) can also be represented as a polysiloxane having a structural unit represented by general formula (8).

[0034] [ka]

[0035] In the general formulas (1) and (8), R 1 R represents a hydrogen atom, an alkyl group, a cycloalkyl group, a heterocyclic group, an aryl group, a heteroaryl group, or an alkenyl group. 2 represents a hydrogen atom, an alkyl group, a cycloalkyl group, or a silyl group. m represents 0 or 1. 1 represents an organic group containing at least two of a carboxyl group, a sulfo group, a thiol group, a phenolic hydroxyl group, or a derivative thereof. However, when the derivative is a cyclic condensation structure of two of the carboxyl group, the sulfo group, the thiol group, and the phenolic hydroxyl group, A 1 represents an organic group having at least one cyclic condensed structure.

[0036] The alkyl group refers to a saturated aliphatic hydrocarbon group such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, or a tert-butyl group, and may or may not have a substituent. The substituent is not particularly limited, and may be, for example, an alkoxy group, an aryl group, or a heteroaryl group. These substituents may further have a substituent. The number of carbon atoms of the alkyl group is not particularly limited, but is preferably 1 to 20, more preferably 1 to 8, from the viewpoint of availability and cost.

[0037] The cycloalkyl group refers to a saturated alicyclic hydrocarbon group such as a cyclopropyl group, a cyclohexyl group, a norbornyl group, or an adamantyl group, and may or may not have a substituent. The substituent is not particularly limited, and may be, for example, an alkyl group, an alkoxy group, an aryl group, or a heteroaryl group. These substituents may further have a substituent. The explanation of these substituents is common to the following description. The number of carbon atoms in the cycloalkyl group is not particularly limited, but is preferably in the range of 3 to 20.

[0038] The heterocyclic group refers to a group derived from an aliphatic ring having an atom other than carbon in the ring, such as a pyran ring, a piperidine ring, an amide ring, etc., and may or may not have a substituent. The number of carbon atoms in the heterocyclic group is not particularly limited, but is preferably in the range of 2 to 20.

[0039] The aryl group refers to an aromatic hydrocarbon group such as a phenyl group, a naphthyl group, a biphenyl group, an anthracenyl group, a phenanthryl group, a terphenyl group, a pyrenyl group, etc., which may or may not have a substituent. The number of carbon atoms in the aryl group is not particularly limited, but is preferably in the range of 6 to 40.

[0040] The heteroaryl group refers to an aromatic group having one or more atoms other than carbon in the ring, such as a furanyl group, a thiophenyl group, a benzofuranyl group, a dibenzofuranyl group, a pyridyl group, a quinolinyl group, etc., which may or may not have a substituent. The number of carbon atoms in the heteroaryl group is not particularly limited, but is preferably in the range of 2 to 30.

[0041] The alkenyl group refers to an unsaturated aliphatic hydrocarbon group containing a double bond, such as a vinyl group, an allyl group, a butadienyl group, etc., which may or may not have a substituent. The number of carbon atoms in the alkenyl group is not particularly limited, but is preferably in the range of 2 to 20.

[0042] The alkoxy group mentioned above as a substituent refers to a functional group in which one side of an ether bond is substituted with an aliphatic hydrocarbon group, such as a methoxy group, an ethoxy group, a propoxy group, etc., and this aliphatic hydrocarbon group may or may not have a substituent. The number of carbon atoms in the alkoxy group is not particularly limited, but is preferably in the range of 1 to 20.

[0043] A 1 The organic group in represents the above-mentioned alkyl group, cycloalkyl group, heterocyclic group, aryl group, heteroaryl group, or alkenyl group. Among these, from the viewpoint of low hysteresis, alkyl group, cycloalkyl group, aryl group, and alkenyl group are preferred, alkyl group and aryl group are more preferred, and alkyl group is further preferred.

[0044] The polysiloxane having a structural unit represented by the general formula (1) or (8) is A 1 By containing an organic group containing at least two of a carboxyl group, a sulfo group, a thiol group, a phenolic hydroxyl group, or a derivative thereof as the functional group, a solution containing an organic semiconductor such as pentacene or a polythiophene derivative, or a semiconductor such as CNT can be smoothly applied onto the cured film, making it possible to form a uniform semiconductor layer. This is presumably because these polar functional groups present in the cured film control the wettability of the semiconductor solution, enabling application without repellency.

[0045] In addition, when the above-mentioned derivative has a cyclic condensation structure formed by two of the above-mentioned carboxyl group, sulfo group, thiol group and phenolic hydroxyl group, A 1 The same effect can be obtained by containing an organic group having at least one cyclic condensed structure as the cyclic condensed structure.

[0046] In addition, the polysiloxane having a structural unit represented by the general formula (1) or (8) is A 1 By having this, the crack resistance of the obtained cured film is increased, and the leakage current of the element is reduced.

[0047] Furthermore, the polysiloxane having a structural unit represented by the general formula (1) or (8) is A 1 By having this, the cured film exhibits excellent solubility in an alkaline developer during lithography. This makes it possible to process a pattern with high precision according to the design dimensions, resulting in good resolution. The resolution is preferably 30 μm or less, more preferably 15 μm or less, and even more preferably 5 μm or less.

[0048] Among the derivatives of a carboxyl group, a sulfo group, a thiol group, or a phenolic hydroxyl group, examples of the non-cyclic condensed structure include carboxylates, sulfonate esters, thioesters, thioethers, and phenyl ethers with a hydrocarbon group or a silyl group, etc. In addition, examples include amide compounds or imide compounds generated by the reaction of a carboxylic acid anhydride with an amine compound, and the like.

[0049] Here, the silyl group is not particularly limited as long as it is a functional group with a silicon atom as a bonding point, and may have a hydrogen group, an organic group, and further a silyl group, and may be bonded via an oxygen atom. Polysiloxane is also possible.

[0050] Examples of the cyclic condensation structure formed by two of a carboxyl group, a sulfo group, a thiol group, and a phenolic hydroxyl group include a cyclic acid anhydride structure, a cyclic ester structure, a cyclic thioester structure, a cyclic ether structure, and a cyclic thioether structure.

[0051] The condensation includes both intramolecular condensation and condensation between other molecules. In the case of condensation between other molecules, it includes both condensation between polysiloxanes and condensation between other constituent materials.

[0052] A in general formulas (1) and (8) 1 From the viewpoint of improving the coatability of the semiconductor solution and reducing leakage current of the element by improving the crack resistance of the cured film, an organic group having at least two carboxyl groups or derivatives thereof, or at least one cyclic acid anhydride group is preferred. 1As the group, a group represented by general formula (2) or (3) is more preferable.

[0053] [ka]

[0054] In the general formula (2), X 1 represents a single bond, an alkylene group having 1 to 10 carbon atoms, or an arylene group having 6 to 15 carbon atoms. 3 and R 4 Each of X independently represents a hydrogen atom, an organic group, or a silyl group. 2 represents a single bond, an alkylene group having 1 to 10 carbon atoms, or an arylene group having 6 to 15 carbon atoms.

[0055] In the polysiloxane, the content ratio of the structural unit represented by the general formula (1) or (8) in the total silane structural units is preferably 0.5 mol% or more, more preferably 1.0 mol% or more, and even more preferably 1.5 mol% or more from the viewpoints of improving the coating property of the semiconductor solution, reducing the leakage current of the element by improving the crack resistance of the cured film, and improving the resolution during lithography of the cured film. Also, from the viewpoint of preventing an increase in the leakage current due to moisture absorption, it is preferably 25 mol% or less, more preferably 20 mol% or less, and even more preferably 15 mol% or less.

[0056] The content ratio of the structural unit represented by the general formula (1) or (8) in the total silane structural units in the polysiloxane is 13It can be determined by C-NMR. In the case of carboxyl groups and their derivatives, the carbon atom of the carbonyl appears at a chemical shift of around 170-180 ppm, in the case of sulfo groups and their derivatives, the carbon atom bonded to the S atom appears at a chemical shift of around 30-40 ppm, in the case of thiol groups and their derivatives, the carbon atom bonded to the S atom appears at a chemical shift of around 10-20 ppm, and in the case of phenolic hydroxyl groups and their derivatives, the carbon atom in the aromatic ring bonded to the O atom derived from the phenolic hydroxyl group appears at a chemical shift of around 140-170 ppm. The content ratio of the structural unit can be determined from the peak area ratio of the carbon atoms in these and other structural units.

[0057] Examples of the structural units represented by the general formulas (1) and (8) include structural units derived from the following silane compounds.

[0058] Examples of compounds having a carboxyl group or a derivative thereof include dimethoxymethylsilylmethylsuccinic acid, diethoxymethylsilylmethylsuccinic acid, dimethoxyphenylsilylmethylsuccinic acid, diethoxyphenylsilylmethylsuccinic acid, trimethoxysilylmethylsuccinic acid, triethoxysilylmethylsuccinic acid, 2-dimethoxymethylsilylethylsuccinic acid, 2-diethoxymethylsilylethylsuccinic acid, 2-dimethoxyphenylsilylethylsuccinic acid, 2-diethoxyphenylsilylethylsuccinic acid, Diphenylsilylethyl succinic acid, 2-trimethoxysilylethyl succinic acid, 2-triethoxysilylethyl succinic acid, 3-dimethoxymethylsilylpropyl succinic acid, 3-diethoxymethylsilylpropyl succinic acid, 3-dimethoxyphenylsilylpropyl succinic acid, 3-diethoxyphenylsilylpropyl succinic acid, 3-trimethoxysilylpropyl succinic acid, 3-triethoxysilylpropyl succinic acid, 4-dimethoxymethylsilylbutyl succinic acid, 4-diethoxyphenylsilylpropyl succinic acid 4-Dimethoxyphenylsilyl butylsuccinic acid, 4-Diethoxyphenylsilyl butylsuccinic acid, 4-Trimethoxysilyl butylsuccinic acid, 4-Triethoxysilyl butylsuccinic acid, 5-Dimethoxymethylsilyl pentylsuccinic acid, 5-Diethoxymethylsilyl pentylsuccinic acid, 5-Dimethoxyphenylsilyl pentylsuccinic acid, 5-Diethoxyphenylsilyl pentylsuccinic acid, 5-Diethoxyphenylsilyl pentylsuccinic acid, 5-Trimethoxysilyl pentylsuccinic acid, Examples of such compounds include 5-triethoxysilylpentylsuccinic acid, 6-dimethoxymethylsilylhexylsuccinic acid, 6-diethoxymethylsilylhexylsuccinic acid, 6-dimethoxyphenylsilylhexylsuccinic acid, 6-diethoxyphenylsilylhexylsuccinic acid, 6-trimethoxysilylhexylsuccinic acid, 6-trimethoxysilylhexylsuccinic acid, and structural units derived from compounds in which these succinic acids have become glutaric acid.

[0059] Examples of those having a sulfo group or a derivative thereof include structural units derived from 5-dimethoxymethylsilylpentane-1,2-disulfonic acid, 5-diethoxymethylsilylpentane-1,2-disulfonic acid, 5-dimethoxyphenylsilylpentane-1,2-disulfonic acid, 5-diethoxyphenylsilylpentane-1,2-disulfonic acid, 5-trimethoxysilylpentane-1,2-disulfonic acid, 5-triethoxysilylpentane-1,2-disulfonic acid, and their methyl esters, ethyl esters, n-propyl esters, isopropyl esters, n-butyl esters, sec-butyl esters, and t-butyl esters.

[0060] Examples of those having a thiol group or a derivative thereof include 3-(3-dimethoxymethylsilylpropyloxy)propane-1,2-dithiol, 3-(3-diethoxymethylsilylpropyloxy)propane-1,2-dithiol, 3-(3-dimethoxyphenylsilylpropyloxy)propane-1,2-dithiol, 3-(3-diethoxyphenylsilylpropyloxy)propane-1,2-dithiol, 3-(3-trimethoxysilylpropyloxy)propane-1,2-dithiol, 3-(3-triethoxysilylpropyloxy)propane-1,2-dithiol, and structural units derived from these methyl thioethers, ethyl thioethers, n-propyl thioethers, isopropyl thioethers, n-butyl thioethers, sec-butyl thioethers, and t-butyl thioethers.

[0061] Examples of compounds having a phenolic hydroxyl group or a derivative thereof include structural units derived from catechol, resorcinol, hydroquinone, or phloroglucinol having a 3-dimethoxymethylsilylpropyl group, a 3-diethoxymethylsilylpropyl group, a 3-dimethoxyphenylsilylpropyl group, a 3-diethoxyphenylsilylpropyl group, a 3-trimethoxysilylpropyl group, or a 3-triethoxysilylpropyl group, as well as the methyl ether, ethyl ether, n-propyl ether, isopropyl ether, n-butyl ether, sec-butyl ether, and t-butyl ether thereof.

[0062] Examples of compounds containing one each of different types of groups among carboxyl groups, sulfo groups, thiol groups, phenolic hydroxyl groups, and derivatives thereof include 1-carboxyl-2-sulfo-5-trimethoxysilylpentane, 1-carboxyl-2-mercapto-5-trimethoxysilylpentane, 1-sulfo-2-mercapto-5-trimethoxysilylpentane, 1-carboxyl-2-hydroxy-4-trimethoxysilylbenzene, 1-sulfo-2-hydroxy-4-trimethoxysilylbenzene, 1-mercapto-2-hydroxy-4-trimethoxysilylbenzene, and the like. These include positional isomers having different positions of the substituents, as well as structural units derived from methyl(thio)esters, ethyl(thio)esters, n-propyl(thio)esters, isopropyl(thio)esters, n-butyl(thio)esters, sec-butyl(thio)esters, t-butyl(thio)esters, methyl(thio)ethers, ethyl(thio)ethers, n-propyl(thio)ethers, isopropyl(thio)ethers, n-butyl(thio)ethers, sec-butyl(thio)ethers, t-butyl(thio)ethers, cyclic(thio)esters, and cyclic(thio)ethers. Among them, from the viewpoint of improving the coating property of the semiconductor solution and reducing the leakage current of the element by improving the crack resistance of the cured film, a structural unit derived from a silane compound having at least two carboxyl groups or derivatives thereof, or at least one cyclic acid anhydride group is preferred, a structural unit derived from a silane compound having succinic acid, a succinic anhydride structure, or a derivative thereof is more preferred, and a structural unit derived from a silane compound having a succinic acid or succinic anhydride structure is even more preferred.Specifically, a structural unit derived from 3-dimethoxymethylsilylpropylsuccinic acid, 3-diethoxymethylsilylpropylsuccinic acid, 3-dimethoxyphenylsilylpropylsuccinic acid, 3-diethoxyphenylsilylpropylsuccinic acid, 3-trimethoxysilylpropylsuccinic acid, 3-triethoxysilylpropylsuccinic acid, and anhydrides thereof is more preferred, and a structural unit derived from 3-trimethoxysilylpropylsuccinic acid, 3-triethoxysilylpropylsuccinic acid, and anhydrides thereof is particularly preferred.

[0063] From the viewpoint of achieving both high insulating properties and crack resistance, it is preferable that the polysiloxane in the cured film further contains at least one structural unit other than the general formulas (1) and (8). Here, the insulating property in the present invention is an index of the difficulty of electricity passing through, and is a value having a volume resistivity of 10 8 This means that the resistance is Ω·cm or more.

[0064] Examples of structural units other than those represented by general formulas (1) and (8) include known structural units such as those described in WO 2019 / 065561.

[0065] (Production method of polymer A) Polymer A can be obtained, for example, by the following method. Here, the case of polysiloxane is taken as an example. After all silane compounds and inorganic particles are put into a solvent, the mixture is stirred, and an acid catalyst and water are added thereto over 1 to 180 minutes, followed by hydrolysis reaction at 15 to 80°C for 1 to 180 minutes. The temperature during the hydrolysis reaction is more preferably 15 to 55°C. The obtained reaction liquid is further heated at 50°C or higher and below the boiling point of the solvent for 1 to 100 hours to carry out a condensation reaction, thereby obtaining polysiloxane to which inorganic particles are bonded. In this way, a method of hydrolyzing a silane compound in the presence of inorganic particles and dehydrating and condensing the silane compound can be mentioned.

[0066] Various conditions for the hydrolysis reaction can be set, for example, acid concentration, reaction temperature, reaction time, etc., taking into consideration the reaction scale, the size and shape of the reaction vessel, etc., so that physical properties suitable for the intended application can be obtained.

[0067] Examples of the acid catalyst used in the hydrolysis reaction of the silane compound include formic acid, oxalic acid, hydrochloric acid, sulfuric acid, acetic acid, trifluoroacetic acid, phosphoric acid, polyphosphoric acid, polycarboxylic acid or its anhydride, and ion exchange resin. The content of the acid catalyst is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, based on 100 parts by mass of the total silane compound that is the raw material of the polysiloxane. The content of the acid catalyst is preferably 10 parts by mass or less, more preferably 5 parts by mass or less. If the content of the acid catalyst is 0.05 parts by mass or more, the hydrolysis reaction proceeds sufficiently, and if it is 10 parts by mass or less, a rapid reaction can be suppressed.

[0068] From the viewpoint of storage stability, it is preferable that the polysiloxane does not contain the acid catalyst, so the catalyst may be removed after the hydrolysis reaction. As a method for removing the catalyst, from the viewpoint of ease of operation and removability, washing with water or treatment with ion exchange resin is preferable. Here, washing with water refers to a method in which the polysiloxane solution is diluted with a suitable hydrophobic solvent, washed with water several times, and the obtained organic layer is concentrated with an evaporator or the like. Moreover, treatment with ion exchange resin refers to a method in which the obtained polysiloxane solution is brought into contact with an ion exchange resin.

[0069] The solvent used in the hydrolysis reaction is preferably an organic solvent, and examples of the solvent include alcohols such as ethanol, propanol, butanol, and 3-methyl-3-methoxy-1-butanol; glycols such as ethylene glycol and propylene glycol; ethers such as ethylene glycol monomethyl ether, propylene glycol monomethyl ether, propylene glycol monobutyl ether, and diethyl ether; ketones such as methyl isobutyl ketone and diisobutyl ketone; amides such as dimethylformamide and dimethylacetamide; acetates such as ethyl acetate, ethyl cellosolve acetate, and 3-methyl-3-methoxy-1-butanol acetate; aromatic or aliphatic hydrocarbons such as toluene, xylene, hexane, and cyclohexane, as well as γ-butyrolactone, N-methyl-2-pyrrolidone, and dimethylsulfoxide. The amount of the solvent is preferably in the range of 50 parts by mass to 500 parts by mass relative to 100 parts by mass of the total silane compounds that are the raw materials for polysiloxane. When the amount is 50 parts by mass or more, a rapid reaction can be suppressed, and when the amount is 500 parts by mass or less, the hydrolysis can be allowed to proceed sufficiently.

[0070] In addition, the water used for hydrolysis is preferably ion-exchanged water.The amount of water can be selected arbitrarily, but in addition to the water equivalent to the alkoxy group in the silane compound, when using a silane compound having a hydrolyzable structure such as an acid anhydride group or an epoxy group, it is better to further add water equivalent to or more than the functional group to be hydrolyzed.In order to increase the degree of polymerization of polysiloxane, it is also possible to reheat or add a base catalyst.

[0071] Whether or not a polysiloxane contains a structural unit represented by general formula (1) or (8) can be determined by various organic analysis methods, such as elemental analysis, nuclear magnetic resonance analysis, and infrared spectroscopy, either alone or in combination.

[0072] (Polymer B: a polymer that is not bonded to inorganic particles and has functional groups capable of forming hydrogen bonds with hydroxyl groups on the surface of inorganic particles contained in Polymer A) When the polymer contained in the resin composition is only polymer A, the thickness of the cured film of the resin composition formed around the lower electrode and on the lower electrode becomes uneven. For this reason, in the case of FET, the thickness of the gate insulating film becomes uneven, and the element does not work due to gate leakage at the thin film area, and the on-current becomes low at the thick film area, resulting in a decrease in element characteristics. Furthermore, in a substrate having multiple FETs, the unevenness of the film thickness increases the variation of element characteristics within the substrate. On the other hand, in the case of a capacitor, if the area of ​​the lower electrode is large and the unevenness of the film thickness of the cured film of the resin composition on the electrode increases, leakage occurs at the thin film area, and the yield of element formation is significantly reduced. Furthermore, the unevenness of the film thickness increases the variation of element characteristics such as capacitance value within the substrate.

[0073] The above-mentioned unevenness in film thickness is presumed to be due to poor leveling near the lower electrode, caused by low liquid fluidity of the varnish of polymer A when it is applied or dried. This is presumed to be due to the inclusion of inorganic particles in polymer A. Therefore, when polymer B was added to improve the liquid fluidity of the varnish of polymer A, it was found that the above-mentioned unevenness in film thickness was improved.

[0074] There are no particular limitations on the polymer B as long as it has a functional group capable of hydrogen bonding with the hydroxyl group on the surface of the inorganic particles contained in the polymer A, and various polymers can be used, such as polysiloxane, polyamide, polyamideimide, polyimide, polybenzimidazole, polyvinyl alcohol, polyhydroxystyrene, polyacetal, polycarbonate, polyarylate, polyphenylene sulfide, polyethersulfone, polyetherketone, polyphthalamide, polyethernitrile, polymethyl methacrylate, polymethacrylamide, aromatic polyether, novolac resin, phenol resin, acrylic resin, epoxy resin, melamine resin, urea resin, etc. Furthermore, these polymers can be copolymerized or mixed with other polymers.

[0075] If a polymer is used that does not have functional groups capable of forming hydrogen bonds with the hydroxyl groups on the surface of the inorganic particles contained in polymer A, the dispersibility of polymer A in the varnish will decrease, the inorganic particles will precipitate, and a uniform film will not be obtained.

[0076] Polymer B is preferably a polymer having at least one type of functional group selected from the group consisting of a carboxyl group, a sulfo group, a phosphate group, a mercapto group, a hydroxyl group, an epoxy group, and derivatives thereof, and is particularly preferably at least one selected from the group consisting of polysiloxanes having a structural unit represented by formula (4), resins having a phenolic hydroxyl group, polyesters having a carboxylic acid residue represented by formula (5), and polymaleic acid and derivatives thereof.

[0077] [ka]

[0078] The polysiloxane having a structural unit represented by general formula (4) can also be represented as a polysiloxane having a structural unit represented by general formula (9).

[0079] [ka]

[0080] In the general formulas (4) and (9), R 5 R represents a hydrogen atom, an alkyl group, a cycloalkyl group, a heterocyclic group, an aryl group, a heteroaryl group, or an alkenyl group. 6 represents a hydrogen atom, an alkyl group, a cycloalkyl group, or a silyl group. n represents 0 or 1. A 2 represents an organic group containing at least one of a carboxyl group, a sulfo group, a thiol group, a phenolic hydroxyl group, an epoxy group, or a derivative thereof. However, when the derivative is a cyclic condensation structure of any two of the carboxyl group, the sulfo group, the thiol group, and the phenolic hydroxyl group, A 2represents an organic group having at least one cyclic condensed structure.

[0081] Of the structural units represented by general formulae (4) and (9), the structural units derived from a silane compound containing a carboxyl group can be the same as those represented by the above-mentioned general formulae (1) and (8).

[0082] As the structural units represented by the general formulas (4) and (9), those having a sulfo group or a derivative thereof, those having a thiol group or a derivative thereof, those having a phenolic hydroxyl group or a derivative thereof, and those having one each of different types of groups among a carboxyl group, a sulfo group, a thiol group, a phenolic hydroxyl group, or a derivative thereof, the same as those represented by the general formulas (1) and (8) described above can be used.

[0083] Among the structural units represented by general formulas (4) and (9), examples of structural units derived from silane compounds containing an epoxy group include structural units derived from silane compounds such as β-glycidoxyethyltrimethoxysilane, β-glycidoxyethyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, γ-glycidoxypropylphenyldimethoxysilane, γ-glycidoxypropylcyclohexyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethylphenyldimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethylcyclohexyldimethoxysilane.

[0084] Examples of resins having phenolic hydroxyl groups include polyhydroxystyrene and phenolic resins. The phenolic resins are generally monomers, oligomers, and polymers having two or more phenolic hydroxyl groups in one molecule, and are not particularly limited in terms of molecular weight or molecular structure. Examples of the phenolic resins include novolac-type resins such as phenol novolac resins, cresol novolac resins, and naphthol novolac resins; multifunctional phenolic resins such as triphenolmethane-type phenolic resins; modified phenolic resins such as terpene-modified phenolic resins and dicyclopentadiene-modified phenolic resins; and aralkyl-type resins such as phenol aralkyl resins having a phenylene skeleton and / or biphenylene skeleton and naphthol aralkyl resins having a phenylene skeleton and / or biphenylene skeleton.

[0085] [ka]

[0086] In the general formula (5), R 7 represents a hydrogen atom, an alkyl group, a cycloalkyl group, a heterocyclic group, an aryl group, a heteroaryl group, an alkenyl group, or an organic group represented by general formula (6).

[0087] [ka]

[0088] In the general formula (6), R 8 represents a hydroxyl group, an alkoxy group, or a functional group represented by general formula (7).

[0089] [ka]

[0090] In the general formula (7), R 9R represents a functional group represented by an alkylene group or an oxyalkylene group. However, the alkylene group or the oxyalkylene group may contain at least one ester bond, amide bond, or urethane bond. 10 represents a hydrogen atom or a methyl group.

[0091] The presence of an unsaturated bond as in general formula (7) enables addition reactions between the polymers and / or with the acrylic group and / or methacrylic group contained in the radically polymerizable compound described below. As a result, a crosslinked structure is formed between the polymers, making the insulating film denser and improving the crack resistance, solvent resistance, etc.

[0092] Examples of polyester materials having a carboxylic acid residue represented by general formula (5) include WR-301 (manufactured by ADEKA CORPORATION), V-259ME (trade name) (manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.), FINE-DIC M-8842, FINE-DIC M-8843, FINE-DIC M-8860, FINE-DIC M-8961 (manufactured by DIC Corporation), etc. These may be used alone or in combination of two or more kinds.

[0093] The polyester material having a carboxylic acid residue represented by the general formula (5) can be synthesized by an esterification reaction between the acid anhydride group of tetracarboxylic dianhydride and the hydroxyl group of a diol compound.

[0094] The tetracarboxylic dianhydride is not particularly limited, but examples thereof include, but are not limited to, pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-oxydiphthalic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, and derivatives thereof. In addition, one type may be used alone, or two or more types may be used in combination.

[0095] The diol compound is not particularly limited, but examples thereof include 1,3-propanediol, 1,2-propanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, hydrogenated bisphenol A, etc. Furthermore, examples of commercially available products include Kuraray Polyol C-1015N (manufactured by Kuraray Co., Ltd.), Kuraray Polyol C-1065N (manufactured by Kuraray Co., Ltd.), DURANOL-T5651 (manufactured by Asahi Kasei Chemicals Co., Ltd.), etc., but are not limited thereto. In addition, one type may be used alone, or two or more types may be used in combination.

[0096] The structure of general formula (7) can be introduced by reacting a hydroxyl group-containing (meth)acrylate compound with the carboxyl group of general formula (5). The hydroxyl group-containing (meth)acrylate compound is not particularly limited, and examples thereof include, but are not limited to, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, 1,4-cyclohexanedimethanol mono(meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxyethyl-phthalic acid, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, and glycerol mono(meth)acrylate. In addition, one type may be used alone, or two or more types may be used in combination.

[0097] Examples of polymaleic acid and its derivatives include, but are not limited to, polymaleic acid, isobutylene-maleic anhydride copolymer, styrene-maleic anhydride copolymer, methyl vinyl ether-maleic anhydride copolymer, α-methylstyrene-maleic anhydride copolymer, rosin-modified maleic acid resin, and those in which a part or all of the carboxyl groups of these are esterified, Marquid, Traffics, Arastar (all trade names, manufactured by Arakawa Chemical Industries, Ltd.), X-288, X-220, US-1243, X-200, X-205 (all trade names, manufactured by Seiko PMC Co., Ltd.), etc. Furthermore, these may be used alone or in combination of two or more kinds.

[0098] The content of polymer B is not particularly limited, but from the viewpoint of improving the unevenness of the thickness of the cured film on and around the electrode, it is preferably 5 parts by weight or more, and more preferably 8 parts by weight or more, relative to 100 parts by weight of the total of polymer A and polymer B. On the other hand, from the viewpoint of controlling the solubility in an alkaline developer during photolithography processing described later and maintaining the high dielectric property derived from the inorganic particles contained in polymer A, it is preferably 60 parts by weight or less, more preferably 30 parts by weight or less, and even more preferably 20 parts by weight or less.

[0099] By being within these ranges, the contrast between the exposed and unexposed parts can be obtained during photolithography while maintaining a high dielectric constant of the cured film. "Contrast between the exposed and unexposed parts can be obtained" means, for example, in the case of a positive photosensitive material, that no film remains in the exposed parts, and the solubility in the developer of the unexposed parts is suppressed, leaving a cured film of a desired thickness.

[0100] The content of the inorganic particles relative to 100 parts by weight of the total of polymer A and polymer B is not particularly limited, but from the viewpoint of increasing the dielectric constant of the cured film, it is preferably 15 parts by weight or more, and particularly preferably 30 parts by weight or more, while from the viewpoint of dispersibility of polymer A in a solution state, it is preferably 80 parts by weight or less.

[0101] The presence of polymer A and polymer B in the resin composition was confirmed by FT-IR and1 H-NMR, 13 C-NMR, 29 Analysis can be performed by combining analytical techniques such as Si-NMR, pyrolysis GC-MS, and LC-MS.

[0102] (solvent) The solvent used in the resin composition of the present invention is not particularly limited, and examples thereof include alcohols such as acetol, 3-hydroxy-3-methyl-2-butanone, 4-hydroxy-3-methyl-2-butanone, 5-hydroxy-2-pentanone, 4-hydroxy-4-methyl-2-pentanone (diacetone alcohol), ethyl lactate (boiling point: 151° C.), butyl lactate (boiling point: 186° C.), propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono n-propyl ether, propylene glycol mono n-butyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, dipropylene glycol monomethyl ether, 3-methoxy-1-butanol, and 3-methyl-3-methoxy-1-butanol; Examples of the ethyl acetate include ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, propylene glycol monomethyl ether acetate, 3-methoxy-1-butyl acetate, 3-methyl-3-methoxy-1-butyl acetate, esters such as ethyl acetoacetate, methyl isobutyl ketone, diisopropyl ketone, diisobutyl ketone, ketones such as acetylacetone, ethers such as diethyl ether, diisopropyl ether, di-n-butyl ether, diphenyl ether, diethylene glycol ethyl methyl ether, diethylene glycol dimethyl ether, γ-butyrolactone, γ-valerolactone, δ-valerolactone, propylene carbonate, N-methylpyrrolidone, cyclopentanone, cyclohexanone, cycloheptanone, etc., and may contain two or more of these. Among these, it is preferable to contain alcohols from the viewpoint of dispersibility of inorganic particles.

[0103] (Photosensitive organic component) As described later, when forming an element using the resin composition of the present invention, it is preferable to subject the cured film to pattern processing by photolithography, and it is preferable that the resin composition of the present invention contains a photosensitive organic component. Examples of the photosensitive organic component include a radical polymerizable compound having an ethylenically unsaturated double bond group, a photopolymerization initiator that generates radicals by bond cleavage and / or reaction upon irradiation with UV light, a chain transfer agent, a polymerization inhibitor, and a photoacid generator that generates acid by light.

[0104] From the viewpoint of reducing hysteresis in FET elements, it is preferable to use a photoacid generator that does not generate radicals that cause charge trapping in the gate insulating film. By reducing charge trapping in the gate insulating film, it is possible to achieve low hysteresis.

[0105] The photoacid generator is not particularly limited, but examples thereof include onium salt compounds, halogen-containing compounds, diazoketone compounds, diazomethane compounds, sulfone compounds, sulfonic acid ester compounds, and sulfonimide compounds. Specific examples of diazoketone compounds include 1,3-diketo-2-diazo compounds, diazobenzoquinone compounds, and diazonaphthoquinone compounds. Among them, diazonaphthoquinone compounds are preferred from the viewpoint of pattern processing accuracy and crack resistance of the resulting cured film. Preferred diazoketone compounds include esters of 1,2-naphthoquinone diazide-4-sulfonic acid and 2,2,3,4,4'-pentahydroxybenzophenone, and esters of 1,2-naphthoquinone diazide-4-sulfonic acid and 1,1,1-tris(4-hydroxyphenyl)ethane.

[0106] (Other Ingredients) The resin composition of the present invention may further contain inorganic particles to which no polymer is bonded, in addition to the polymer to which the inorganic particles are bonded. The preferred materials and shapes of the inorganic particles to which no polymer is bonded are the same as those of the inorganic particles to which the polymer is bonded.

[0107] Furthermore, the resin composition of the present invention may contain, as necessary, a viscosity modifier, a surfactant, a stabilizer, etc. Furthermore, it may contain a residual solvent.

[0108] In particular, it is preferable to include a surfactant from the viewpoint of improving the coating property of the resin composition. There is no particular limitation on the type of surfactant, and for example, fluorine-based surfactants such as "Megafac (registered trademark)" F142D, F172, F173, F183, F445, F470, F475, and F477 (all manufactured by Dai Nippon Ink and Chemicals Co., Ltd.), NBX-15, FTX-218, and DFX-18 (manufactured by Neos Co., Ltd.), silicone-based surfactants such as BYK-333, BYK-301, BYK-331, BYK-345, and BYK-307 (manufactured by BYK-Chemie Japan Co., Ltd.), polyalkylene oxide-based surfactants, and poly(meth)acrylate-based surfactants can be used. Two or more of these may be used. Among these, fluorine-based surfactants are particularly preferred.

[0109] <Element> Examples of elements formed using the resin composition of the present invention include field effect transistors (FETs) and capacitors.

[0110] The FET is an element having a gate electrode, a gate insulating film, a source electrode, a drain electrode, and a semiconductor layer in contact with the source electrode and the drain electrode, and the gate insulating film can be obtained by applying and drying the resin composition of the present invention.

[0111] The capacitor is an element having a lower electrode, an upper electrode, and a dielectric film between the lower electrode and the upper electrode, and the dielectric film can be obtained by applying and drying the resin composition of the present invention.

[0112] An example of a method for producing such an element is as follows. (Production Example 1) A method for manufacturing an element, comprising the following steps 1 to 3: (Step 1) A step of forming a conductive pattern that will become the lower electrode on a substrate (Step 2) applying the resin composition according to any one of claims 1 to 7 onto the substrate on which the conductive pattern has been formed and drying the composition to obtain a coating film; (Step 3) A step of forming a conductive pattern that will become an upper electrode on the coating film. (Production Example 2) A method for manufacturing an element, comprising the following steps 1' to 3'. (Step 1') A step of forming a conductive pattern that will become a lower electrode on a substrate (Step 2') A step of applying the resin composition according to any one of claims 1 to 7 onto the substrate on which the conductive pattern is formed, drying the resin composition to obtain a coating film, and then irradiating the coating film with actinic rays through a photomask and developing the coating film to form a dielectric pattern having an opening on the conductive pattern. (Step 3') A step of forming a conductive pattern that will become an upper electrode on the dielectric pattern.

[0113] Specific examples of elements obtained by using the resin composition of the present invention will be described in more detail below with reference to the drawings. However, the elements obtained by using the resin composition of the present invention are not limited to the following.

[0114] [FET] 1 is a schematic cross-sectional view showing a FET. This structure includes an insulating substrate 100, a gate electrode 11, a gate insulating film 12, a source electrode 13, a drain electrode 15, and a semiconductor layer 14 in contact with the source electrode and the drain electrode. The semiconductor layer and the gate electrode are electrically separated by the gate insulating film.

[0115] 2 to 6 are schematic cross-sectional views showing modified examples of the above-mentioned FET. In Modification 1 shown in FIG. 2, there is no overlap between the gate electrode 11 and the source electrode 13 / drain electrode 15, and the width of the semiconductor layer 14 and the width of the gate electrode are the same. In Modification 2 shown in FIG. 3, there is overlap between the gate electrode 11 and the source electrode 13 / drain electrode 15. In Modification 3 shown in FIG. 4, there is no overlap between the gate electrode 11 and the source electrode 13 / drain electrode 15, and the width of the semiconductor layer 14 is larger than the width of the gate electrode. In Modification 4 shown in FIG. 5, the gate electrode 11 and the source electrode 13 overlap.

[0116] 1 to 5 show examples of a bottom gate structure, whereas Modification 5 shown in FIG. 6 shows a top gate structure in which the gate electrode 11 and the drain electrode 15 overlap each other.

[0117] (Gate insulating film) The gate insulating film preferably has a relative dielectric constant of 4 or more, more preferably 7 or more, even more preferably 8.5 or more, and particularly preferably 10 or more. By having the relative dielectric constant in the above range, the on-current of the FET can be increased. Furthermore, the relative dielectric constant is preferably 20 or less, more preferably 15 or less, even more preferably 13.5 or less, and particularly preferably 12 or less. By having the relative dielectric constant in the above range, excessive dielectric loss due to the gate insulating film can be prevented, and in particular, a FET driven by radio waves in a high frequency band of 100 MHz or more can operate accurately. Relative dielectric constant ε of the gate insulating film r can be calculated using the following formula (a).

[0118] ε r =C D / (S ε0) (a) where C(F) is the capacitance of the gate insulating film, D(m) is the thickness of the gate insulating film, and S(m 2 ) is the area of ​​the electrodes sandwiching the gate insulating film, and ε0 is the dielectric constant of vacuum (8.85×10 -12 F / m).

[0119] The content of the inorganic particles in the gate insulating film is preferably 10 vol% or more, more preferably 15 vol% or more, and particularly preferably 20 vol% or more, in terms of volume fraction, and is preferably 60 vol% or less, more preferably 50 vol% or less, and particularly preferably 40 vol% or less.

[0120] The thickness of the gate insulating film is preferably 10 nm or more, more preferably 25 nm or more, and particularly preferably 50 nm or more. The thickness of the gate insulating film is preferably 1000 nm or less, more preferably 750 nm or less, and particularly preferably 500 nm or less. The gate insulating film is composed of a single layer or multiple layers. In the case of multiple layers, the above-mentioned preferred gate insulating films may be stacked multiple times, or the preferred gate insulating film and a known gate insulating film may be stacked.

[0121] In addition, an orientation layer can be provided between the gate insulating film and the semiconductor layer described below. As the material for the orientation layer, known materials such as silane compounds, titanium compounds, organic acids, and heteroorganic acids can be used, and organic silane compounds are particularly preferred.

[0122] (Second insulating film) The FET of the present invention may have a second insulating film on the side opposite to the gate insulating film with respect to the semiconductor layer described later. Here, the side opposite to the gate insulating film with respect to the semiconductor layer refers to the lower side of the semiconductor layer, for example, when the gate insulating film is on the upper side of the semiconductor layer. This makes it possible to reduce the threshold voltage and hysteresis, and a high-performance FET can be obtained. Preferred examples of the second insulating layer and its manufacturing method include known ones such as those described in International Publication No. 2019 / 065561.

[0123] (Semiconductor layer) The semiconductor layer in the present invention is not particularly limited as long as it has semiconducting properties, and inorganic semiconductors such as silicon semiconductors and oxide semiconductors, organic semiconductors such as pentacene and polythiophene derivatives, and carbon semiconductors such as carbon nanotubes (CNTs) and graphene can be used. Among these, CNTs are superior in that they have high carrier mobility and can be applied to a simple coating process at low cost.

[0124] As the CNT, any of single-walled CNTs in which one carbon film (graphene sheet) is wound in a cylindrical shape, double-walled CNTs in which two graphene sheets are wound concentrically, and multi-walled CNTs in which multiple graphene sheets are wound concentrically may be used, or two or more of these may be used. From the viewpoint of exhibiting semiconductor properties, it is preferable to use single-walled CNTs. It is more preferable that the single-walled CNTs contain 90% by mass or more of semiconducting single-walled CNTs. It is even more preferable that the single-walled CNTs contain 95% by mass or more of semiconducting single-walled CNTs.

[0125] The content ratio of semiconducting single-walled CNTs can be calculated from the absorption area ratio of the visible-near infrared absorption spectrum. CNTs can be obtained by methods such as the arc discharge method, the chemical vapor deposition method (CVD method), and the laser ablation method.

[0126] Furthermore, a CNT composite in which a conjugated polymer is attached to at least a part of the CNT surface is particularly preferred because it has excellent dispersion stability in a solution and low hysteresis. The state in which a conjugated polymer is attached to at least a part of the CNT surface means a state in which the conjugated polymer covers a part or the entire CNT surface. It is presumed that the reason why a conjugated polymer can cover a CNT is because an interaction occurs due to the overlap of π electron clouds derived from each conjugated structure. Whether or not a CNT is covered with a conjugated polymer can be determined by the reflection color of the covered CNT approaching the color of the conjugated polymer from the color of the uncovered CNT. The presence of the deposit and the mass ratio of the deposit to the CNT can be quantitatively identified by elemental analysis, X-ray photoelectron spectroscopy, etc. In addition, the conjugated polymer to be attached to the CNT can be used regardless of the molecular weight, molecular weight distribution, or structure.

[0127] Methods for attaching a conjugated polymer to CNT include (I) adding CNT to a molten conjugated polymer and mixing it, (II) dissolving a conjugated polymer in a solvent and adding CNT to the solution and mixing it, (III) pre-dispersing CNT in a solvent with ultrasonic waves or the like and adding a conjugated polymer to the solution and mixing it, and (IV) putting a conjugated polymer and CNT in a solvent and irradiating the mixture with ultrasonic waves to mix them, etc. A combination of several methods may be used.

[0128] The length of the CNT is preferably shorter than the distance (channel length) between the source electrode and the drain electrode. The average length of the CNT depends on the channel length, but is preferably 2 μm or less, more preferably 0.5 μm or less. Since commercially available CNTs generally have a distribution in length and may contain CNTs longer than the channel length, it is preferable to add a process of shortening the CNT to be shorter than the channel length. For example, a method of cutting the CNT into short fibers by acid treatment with nitric acid, sulfuric acid, or the like, ultrasonic treatment, or freeze-pulverization is effective. In addition, it is more preferable to use separation by a filter in order to improve purity.

[0129] The diameter of the CNT is not particularly limited, but is preferably 1 nm or more and 100 nm or less, and more preferably 50 nm or less.

[0130] It is preferable to provide a step of uniformly dispersing CNTs in a solvent and filtering the dispersion through a filter. By obtaining CNTs smaller than the filter pore size from the filtrate, CNTs shorter than the channel length can be obtained efficiently. In this case, a membrane filter is preferably used as the filter. The pore size of the filter used for filtration should be smaller than the channel length, and is preferably 0.5 to 10 μm.

[0131] Examples of the conjugated polymer that coats the CNT include polythiophene polymers, polypyrrole polymers, polyaniline polymers, polyacetylene polymers, poly-p-phenylene polymers, poly-p-phenylenevinylene polymers, and thiophene-heteroarylene polymers having thiophene units and heteroaryl units in the repeating units, and two or more of these may be used. The above polymers may be those in which a single monomer unit is arranged, those in which different monomer units are block copolymerized, those in which random copolymerization is performed, and those in which graft polymerization is performed.

[0132] The semiconductor layer may be a mixture of a CNT composite and an organic semiconductor. By uniformly dispersing the CNT composite in the organic semiconductor, it is possible to achieve low hysteresis while maintaining the characteristics of the organic semiconductor itself. Preferred organic semiconductors include known ones such as those described in International Publication No. 2019 / 065561.

[0133] The content of the CNT composite in the semiconductor layer containing the CNT composite and the organic semiconductor is preferably 0.01 parts by mass or more and 3 parts by mass or less, and more preferably 1 part by mass or less, per 100 parts by mass of the organic semiconductor.

[0134] The semiconductor layer may also include other carbon materials, such as graphene and fullerene.

[0135] The semiconductor layer may further include an insulating material, such as, but not limited to, polymeric materials such as poly(methyl methacrylate), polycarbonate, and polyethylene terephthalate.

[0136] The semiconductor layer may be a single layer or multiple layers. The thickness of the semiconductor layer is preferably 1 nm to 200 nm, more preferably 100 nm or less. By setting the thickness within this range, it becomes easy to form a uniform thin film, and the variation in FET characteristics can be reduced. The thickness can be measured by an atomic force microscope, an ellipsometry method, or the like.

[0137] (substrate) The material used for the substrate may be any material as long as at least the surface on which the electrodes (gate electrode or source / drain electrodes) are disposed is insulating. For example, inorganic materials such as silicon wafer, glass, sapphire, and sintered alumina, and organic materials such as polyimide, polyvinyl alcohol, polyvinyl chloride, polyethylene terephthalate, polyethylene naphthalate, polyvinylidene fluoride, polysiloxane, polyvinylphenol (PVP), polyester, polycarbonate, polysulfone, polyethersulfone, polyethylene, polyphenylene sulfide, and polyparaxylene are preferably used.

[0138] Alternatively, the substrate may be a laminate of multiple materials, such as a PVP film formed on a silicon wafer, or an acrylic resin, polyester resin, or polysiloxane formed on polyethylene terephthalate as an adhesion improver for the lower electrode.

[0139] Among these, from the viewpoints of element flexibility and manufacturing costs, polyethylene terephthalate (PET) is preferred as the substrate material, and from the viewpoint of the smoothness of the substrate surface in particular, a film in which a coating layer containing silica nanoparticles is formed on the surface of a PET film to which no filler such as silica particles has been added is preferred.

[0140] Regular PET film contains silica particles, which gives the substrate a low surface smoothness, and when devices are fabricated using this film, leakage is likely to occur in the gate insulating film at the convex parts. On the other hand, a film in which a coating layer containing silica nanoparticles is formed on the surface of a PET film to which no fillers such as silica particles have been added has a high surface smoothness. Therefore, devices fabricated using this film are less likely to experience leakage in the gate insulating film.

[0141] (electrode) Examples of materials used for the gate electrode, source electrode, and drain electrode include conductive metal oxides such as tin oxide, indium oxide, and indium tin oxide (ITO); metals such as platinum, gold, silver, copper, iron, tin, zinc, aluminum, indium, chromium, lithium, sodium, potassium, cesium, calcium, magnesium, palladium, molybdenum, amorphous silicon, and polysilicon, and alloys thereof; inorganic conductive substances such as copper iodide and copper sulfide; polythiophene, polypyrrole, and polyaniline; complexes of polyethylenedioxythiophene and polystyrenesulfonic acid; conductive polymers whose conductivity has been improved by doping with iodine or the like; and conductors such as carbon materials. These materials may be used alone, or a plurality of materials may be stacked or mixed for use.

[0142] It is preferable to use metal particles as the conductor. The use of metal particles has the effect of improving the bending resistance of the element. This is thought to be because unevenness is formed on the surface of the conductive film, and the gate insulating film penetrates into the unevenness, resulting in an anchor effect that improves the adhesion between the conductive film and the gate insulating film.

[0143] Specifically, the metal particles are preferably metal particles containing at least one of gold, silver, copper, platinum, lead, tin, nickel, aluminum, tungsten, molybdenum, ruthenium oxide, chromium, titanium, carbon, or indium. These metal particles can be used alone, as an alloy, or as mixed particles. Among these, gold, silver, copper, or platinum particles are preferred from the viewpoint of electrical conductivity. Among these, silver particles are more preferred from the viewpoint of cost and stability. Furthermore, it is even more preferred to contain carbon black from the viewpoint of reducing the electrical resistivity of the conductive film.

[0144] At least one of the gate electrode and the source electrode / drain electrode preferably contains an organic component. By containing an organic component, the adhesion between the electrode and the gate insulating film is improved. In addition, by containing a photosensitive organic component in the organic component, the electrode can be patterned by photolithography without using a resist, and productivity can be further improved. From the viewpoint of further enhancing these effects, it is preferable that both the gate electrode and the source electrode / drain electrode contain an organic component.

[0145] The organic component is not particularly limited, but may be a monomer, an oligomer, or a polymer. The oligomer or polymer is not particularly limited, and may be an acrylic resin, an epoxy resin, a novolac resin, a phenolic resin, a polyimide precursor, or a polyimide, but from the viewpoint of crack resistance when bent, an acrylic resin is preferred. This is presumably because the glass transition temperature of the acrylic resin is 100°C or less, and it softens when the conductive film is thermally cured, strengthening the bond between the conductive particles.

[0146] The photosensitive organic component includes a monomer, oligomer, polymer and / or an addition reaction product thereof having a polymerizable unsaturated group in the molecule.

[0147] As a monomer having a polymerizable unsaturated group in the molecule, a compound having an active carbon-carbon unsaturated double bond can be used. As a functional group, a monofunctional compound having a group selected from a vinyl group, an allyl group, an acrylate group, a methacrylate group, and an acrylamide group and a polyfunctional compound can be used. One or more of these can be used.

[0148] The above monomer is preferably contained in the range of 1 mass % to 15 mass % with respect to the total mass of the electrode material, and more preferably in the range of 2 mass % to 10 mass %. An oligomer or polymer having a polymerizable unsaturated group in the molecule can be obtained by adding the polymerizable unsaturated group to a side chain or a molecular end of an oligomer or polymer.

[0149] The polymerizable unsaturated group is preferably an ethylenically unsaturated group, such as a vinyl group, an allyl group, an acryl group, or a methacryl group.

[0150] Methods for adding such side chains to an oligomer or polymer include known methods, such as those described in WO 2019 / 065561.

[0151] The electrode material preferably contains a photopolymerization initiator for photocuring. The photopolymerization initiator is selected depending on the light source used for photocuring, and a photoradical polymerization initiator, a photocationic polymerization initiator, or the like can be used.

[0152] The photopolymerization initiator is preferably contained in the range of 0.05% by mass to 10% by mass, more preferably 0.1% by mass to 10% by mass, based on the total mass of the electrode material. If the amount of the photopolymerization initiator is too small, photocuring may be insufficient, and if the amount of the photopolymerization initiator is too large, compatibility may be poor.

[0153] By using a sensitizer together with a photopolymerization initiator, the sensitivity can be improved and the wavelength range effective for the reaction can be expanded. When the electrode material contains a sensitizer, the content is preferably 0.05% by mass to 10% by mass, more preferably 0.1% by mass to 10% by mass, based on the photosensitive organic component. If the amount of the sensitizer is too small, the effect of improving photocuring cannot be exhibited, and if the amount of the sensitizer is too large, compatibility may be poor.

[0154] The amount of the conductor in the conductive film is preferably within a range of 70 to 95 wt % of the conductive film, more preferably 80 wt % or more as the lower limit and 90 wt % or less as the upper limit, respectively. By being within this range, the resistivity value and the probability of disconnection of the conductive film can be reduced.

[0155] Examples of methods for forming the electrodes include methods using known techniques such as resistance heating deposition, electron beam, sputtering, plating, CVD, ion plating coating, inkjet, and printing, and methods in which a paste containing the organic component and a conductor is applied onto an insulating substrate by known techniques such as spin coating, blade coating, slit die coating, screen printing, bar coater, casting, print transfer, and immersion and pulling, and then dried using an oven, a hot plate, infrared rays, etc. There are no particular limitations as long as electrical continuity can be obtained.

[0156] When the electrodes are formed by applying a paste, the paste may contain an organic solvent for forming the paste. By using an organic solvent, the viscosity of the paste can be adjusted and the surface smoothness of the applied film can be improved.

[0157] The width, thickness and spacing of the electrodes are arbitrary. It is preferable that the electrode width is 5 μm to 1 mm, the thickness is 0.01 μm to 100 μm, and the spacing between the electrodes is 1 μm to 500 μm, but is not limited to these.

[0158] As a method for forming the electrodes in a pattern, the electrode thin film prepared by the above method may be patterned into a desired shape by a known photolithography method, or the electrode, wiring, and connection material may be patterned through a mask of a desired shape during deposition or sputtering. Alternatively, the pattern may be directly formed by inkjet or printing.

[0159] The electrode patterns may be formed by processing each separately, or at least two of them may be processed together to form the electrode patterns. From the viewpoint of reducing the processing steps and connecting the patterns, it is preferable to process the electrode patterns together.

[0160] (FET manufacturing method) A method for manufacturing the FET shown in Fig. 1 will be described below, although the manufacturing method is not limited to the following.

[0161] (Step 1) A step of forming a conductive pattern that will become the lower electrode on a substrate First, a conductive pattern that will become the gate electrode 11 is formed on the substrate 100. Examples of the formation method include known methods such as metal deposition, spin coating, blade coating, slit die coating, screen printing, bar coating, mold method, print transfer method, immersion and pulling method, and inkjet method. In addition, when forming the conductive pattern, the pattern may be directly formed using a mask or the like, or the gate electrode may be patterned by applying a resist onto the formed gate electrode, exposing and developing the resist film into a desired pattern, and then etching it. Furthermore, when a conductive paste having a photosensitive organic component is used, the gate electrode can be patterned by photolithography without using a resist.

[0162] (Step 2) A step of applying the resin composition of the present invention onto the substrate on which the conductive pattern is formed and drying the composition to obtain a coating film. Next, the gate insulating film 12 is formed on the substrate on which the conductive pattern is formed. The gate insulating film 12 can be formed by applying the resin composition of the present invention onto a substrate, drying the composition to obtain a coating film, and then heating and curing the coating film.

[0163] Examples of a method for applying the resin composition of the present invention include known application methods such as spin coating, blade coating, slit die coating, screen printing, bar coating, casting, print transfer, immersion and pulling, and inkjet methods.

[0164] The drying temperature when obtaining the coating film is preferably 50 to 150°C, more preferably 60 to 140°C, further preferably 70°C to 130°C, and particularly preferably 80°C to 120°C. The drying temperature in this range is preferable from the viewpoint of facilitating removal of the solvent from the coating film and processing into a desired shape during patterning, which will be described later. The drying time is preferably 0.5 to 5 minutes, more preferably 1 to 3 minutes. The drying time in this range is preferable from the viewpoint of facilitating removal of the solvent from the coating film and processing into a desired shape during patterning, which will be described later.

[0165] Furthermore, the temperature of the heat treatment of the coating film to harden the coating film to obtain a gate insulating film is preferably in the range of 100 to 300° C., more preferably 120 to 250° C. When the heat treatment temperature is in this range, a sufficiently hardened gate insulating film can be obtained.

[0166] Furthermore, when a FET is formed on a plastic substrate, the temperature is preferably 120 to 200° C., and particularly preferably 120 to 150° C. When the temperature is within this range, shrinkage of the plastic substrate during heat treatment can be suppressed.

[0167] The time for the heat treatment of the coating film is preferably 0.5 to 60 minutes, more preferably 5 to 30 minutes. By setting the heat treatment time within this range, a sufficiently cured gate insulating film can be obtained.

[0168] (Step 3) forming a conductive pattern that will become an upper electrode on the coating film Next, a conductive pattern that becomes the source electrode 13 and the drain electrode 15 is formed on the gate insulating film. As with the gate electrode 11, the method of forming the source electrode 13 and the drain electrode 15 includes known methods such as metal deposition, spin coating, blade coating, slit die coating, screen printing, bar coating, casting, printing transfer, immersion and pulling, and inkjet. In addition, when forming the conductive pattern, a pattern may be formed directly using a mask or the like, or the source electrode and the drain electrode may be patterned by applying a resist onto the formed electrode, exposing and developing the resist film into a desired pattern, and then etching it. Furthermore, when a conductive paste having a photosensitive organic component is used, it is also possible to pattern the gate electrode by photolithography using only the conductive paste without using a resist.

[0169] The above (Step 1) to (Step 3) can be replaced with (Step 1') to (Step 3').

[0170] In (Step 2'), the same operations as in (Step 2) are performed until a coating film is obtained, and then the coating film can be patterned. When forming a circuit combining FETs, it may be necessary to form a pattern having an opening (contact hole) on the conductive pattern in order to obtain electrical continuity from the conductive pattern present under the insulating layer.

[0171] A method for forming a pattern on a coating film using a composition containing a photosensitive organic component will be described. The coating film is irradiated (exposed) to actinic radiation through a mask having a desired pattern from above. Actinic radiation used for exposure includes ultraviolet light, visible light, electron beams, X-rays, etc., but it is preferable to use i-rays (365 nm), h-rays (405 nm), and g-rays (436 nm) from a mercury lamp. Next, the exposed coating film is developed. Examples of developers include known ones such as tetramethylammonium hydroxide and those described in International Publication No. 2019 / 065561.

[0172] It is also possible to pattern the gate insulating film by applying a resist onto the gate insulating film, exposing and developing the resist film into a desired pattern, and then treating the gate insulating film with an etching solution such as hydrofluoric acid. This method allows patterning even when the gate insulating film is made of a composition that does not contain a photosensitive organic component. However, since the number of steps increases, it is preferable from the viewpoint of excellent productivity to pattern the gate insulating film using an insulating layer material that contains a photosensitive organic component. Furthermore, from the viewpoint of improving the crack resistance of the resulting gate insulating film, After (Step 3) or (Step 3'), a semiconductor layer 14 is formed on the gate insulating film on which the source electrode and drain electrode are formed, thereby obtaining a FET. Although a dry method such as resistance heating deposition, electron beam, sputtering, and CVD can be used as a method for forming the semiconductor layer 14, it is preferable to use a coating method from the viewpoint of manufacturing cost and adaptability to a large area. Examples of the coating method include known coating methods such as spin coating, blade coating, slit die coating, screen printing, bar coating, casting, printing transfer, immersion and pulling, and inkjet. The coating method can be selected according to the coating film characteristics to be obtained, such as coating film thickness control and orientation control. Using these methods, the semiconductor layer is formed so that the semiconductor layer and the conductive pattern that becomes the source electrode 13 and the drain electrode 15 are in contact with each other. The source electrode and the drain electrode may be formed after forming the semiconductor layer.

[0173] In particular, when forming a semiconductor layer containing CNTs, it is preferable to apply a solution containing CNTs onto the gate insulating film. In this case, there is no particular limitation on the application method, but the use of an inkjet method is superior in that it reduces the amount of solution used and increases productivity. The solution containing CNTs can be prepared by stirring CNTs in a solvent through a stirring process using a known dispersion device such as an ultrasonic homogenizer.

[0174] When the semiconductor layer is formed by coating, the formed coating film is dried in air, under reduced pressure, or in an inert gas (nitrogen or argon) atmosphere. The drying temperature is preferably 50 to 150°C.

[0175] A step of forming an orientation layer between the gate insulating film 12 and the semiconductor layer 14 by a method similar to the method of forming a coating film of the above-mentioned gate insulating film material may be added. Also, a step of forming a second insulating layer on the opposite side of the semiconductor layer 14 to the gate insulating film 12 by a method similar to that of the semiconductor layer 14 may be added.

[0176] [Capacitor] 7 is a schematic cross-sectional view showing a capacitor. This structure includes an insulating substrate 200 and a pair of conductive films, a lower electrode 21, a dielectric film 22, and an upper electrode 23. The lower electrode 21 and the upper electrode 23 are not electrically connected, and the dielectric film 22 is formed between the lower electrode 21 and the upper electrode 23. The dielectric film 22 is obtained by applying, drying, and curing the resin composition of the present invention.

[0177] 8 to 10 are schematic cross-sectional views showing modified examples of the above-mentioned capacitor. In Modification 1 shown in Fig. 8, a dielectric film 22 is formed so as to cover a lower electrode 21 on an insulating base material 200, and an upper electrode 23 is further formed so as to cover the dielectric film 22. In Modification 2 shown in Fig. 9, a lower electrode 21 and an upper electrode 23 are present on an insulating base material 200, and a dielectric film 22 is formed therebetween. In Modification 3 shown in Fig. 10, a dielectric film 22 is present so as to cover a part of the upper electrode 21 on an insulating base material 200, and an upper electrode 23 is further formed so as to cover a part of the dielectric film 22.

[0178] Regarding the materials and manufacturing methods of the insulating substrate, dielectric film, upper electrode and lower electrode, the same points as those regarding the insulating substrate, gate insulating film and gate electrode in the above-mentioned FET are applied.

[0179] <Circuit> A circuit can be configured by combining the above FET and capacitor. There are no particular limitations on the circuit, and examples include, but are not limited to, a rectifier circuit, a modulation circuit, a memory circuit, a power supply circuit, a reference voltage / current circuit, a data converter circuit, and an operational amplifier. In addition, these may be used alone or in combination of two or more types.

[0180] FIG. 11 is an example of a rectifier circuit including a FET 301 and a capacitor element 302. In the structure of FIG. 11, a capacitor 302 consisting of a lower electrode 32, an upper electrode 37, and an insulating film (dielectric film) 33, a FET 301 consisting of a gate electrode 31, an insulating film 33 (gate insulating film), a source electrode 35, a drain electrode 36, and a semiconductor layer 34, a wiring 38, and a via 39 are provided on an insulating substrate 300. In FIG. 11, the dielectric film of the capacitor 302 and the gate insulating film of the FET 301 are made common and made of the same material. In FIG. 11, a structure in which the drain electrode 36 and the upper electrode 37 are electrically connected via the wiring 38 are illustrated, but the drain electrode 36 and the lower electrode 32 may be electrically connected via the wiring 38 and the via 39. In addition, although a FET having a bottom gate structure is shown in FIG. 11, a FET having a top gate structure may also be used. Furthermore, in FIG. 11, a circuit is shown in which the dielectric film of the capacitor 302 and the gate insulating film of the FET 301 are common, but as shown in FIGS. 12 and 13, insulating films 33A and 33B made of different materials may be used.

[0181] The insulating substrate, dielectric film, gate electrode, upper electrode, and lower electrode can be made of the same materials and manufactured by the same methods as those used in the first and second embodiments. The vias and wiring can be made of the same materials and manufactured by the same methods as those used in the lower electrode and upper electrode.

[0182] (Applicability of the element) An element manufactured using the resin composition of the present invention can be applied to ICs for various electronic devices, wireless communication devices such as RFID tags, TFT arrays for displays, sensors, tamper detection systems, and the like.

[0183] <Wireless communication device> The circuit manufactured using the resin composition of the present invention can be applied to a wireless communication device. This wireless communication device is a device that performs electrical communication by receiving a carrier wave transmitted from an antenna mounted on a reader / writer, such as a non-contact tag, such as an RFID (Radio Frequency IDentification) tag, for example, a product tag, an anti-shoplifting tag, various tickets, and a smart card. In specific operation, for example, a wireless signal transmitted from an antenna mounted on a reader / writer is received by an antenna of the RFID tag, which is converted to a direct current by a rectifier circuit, and the RFID tag is energized. Next, the energized RFID tag receives a command from the wireless signal and performs an operation according to the command. After that, a response to the command is transmitted as a wireless signal from the antenna of the RFID tag to the antenna of the reader / writer. The operation according to the command is executed by a demodulation circuit, a control circuit, a modulation circuit, etc.

[0184] The wireless communication device of the present invention includes at least the above-mentioned FET and an antenna. A more specific configuration, as shown in FIG. 14, includes a power supply generating unit 45 that rectifies a modulated wave signal received from an external source by an antenna 40 and supplies power to each unit, a demodulation circuit 41 that demodulates the modulated wave signal and sends it to a control circuit, a modulation circuit 43 that modulates data sent from the control circuit and sends it to the antenna, and a control circuit 42 that writes the data demodulated by the demodulation circuit 41 to a memory circuit 44 and reads data from the memory circuit 44 and transmits it to the modulation circuit 43, and the wireless communication device includes each circuit unit electrically connected. At least one of the power supply generating unit, demodulation circuit, control circuit, modulation circuit, and memory circuit includes the above-mentioned elements, and may further include a capacitor, a resistive element, a diode, etc. The memory circuit may further include a read-only memory unit to which information is written during manufacturing, or a non-volatile rewritable memory unit such as an EEPROM (Electrically Erasable Programmable Read-Only Memory) or FeRAM (Ferroelectric Random Access Memory). The power supply generating section is composed of a capacitor and a diode.

[0185] The antenna, capacitor, resistor, diode, and non-volatile rewritable memory unit may be any commonly used material and may have any shape. The material electrically connecting each of them may be any commonly used conductive material. The connection method may be any method that can provide electrical continuity, and the width and thickness of the connection part may be any method.

[0186] <Product tag> A product tag using the wireless communication device will now be described. This product tag has, for example, a base and the wireless communication device covered by the base.

[0187] The base is formed of a non-metallic material such as paper formed into a flat plate shape. For example, the base has a structure in which two flat sheets of paper are pasted together, and the wireless communication device is disposed between the two sheets of paper. Individual identification information for identifying individual products, for example, is stored in advance in a memory circuit of the wireless memory device.

[0188] Wireless communication is performed between this product tag and a reader / writer. A reader / writer is a device that wirelessly reads and writes data to product tags, and exchanges data with product tags during the product distribution process and at the time of payment. Publicly known reader / writers can be used, including, for example, portable types and fixed types installed at cash registers.

[0189] Specifically, the product tag has an identification information return function that wirelessly returns the stored individual identification information in response to a command from a specific reader / writer that requests the transmission of individual identification information. This makes it possible to simultaneously identify multiple products without contact at a product checkout register, for example, and makes payment processing easier and faster than identification using barcodes.

[0190] For example, when paying for a product, the reader / writer can send the product information read from the product tag to a POS (Point of Sale System) terminal, which can then register the sale of the product identified by that product information. EXAMPLES

[0191] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.

[0192] (1) Insulation layer thickness measurement The thickness of the insulating layer on the lower electrode and the thickness of the insulating layer on the insulating substrate around the lower electrode were measured using an optical interference spectroscopic film thickness measuring instrument (OPTM-A2, manufactured by Otsuka Electronics Co., Ltd.). The film thickness was measured at five points on the lower electrode and around the lower electrode, and the difference between the maximum and minimum values ​​was taken as film thickness unevenness, which was evaluated according to the following criteria. A+ (exceptionally good): Film thickness unevenness is less than ±15 nm. A (very good): Film thickness unevenness is less than ±25 nm. B (Good): Film thickness unevenness is between ±25 nm and ±50 nm. C (Acceptable): Film thickness unevenness is between ±50nm and ±100nm. D (Not acceptable): Film thickness unevenness is more than ±100 nm.

[0193] (2) Measurement of the dielectric constant of the insulating layer The insulating solution shown in Table 1 was spin-coated (800 rpm x 10 seconds) onto an aluminum substrate, and then heat-treated at 110°C for 2 minutes, followed by heat-treatment at 150°C for 30 minutes in a drying oven to form a cured film with a thickness of 400 nm. Next, a circular aluminum electrode with a diameter of 5 mm was formed by vapor deposition on the cured film. The electrostatic capacitance of this film was measured at 25°C and 1 MHz using a precision impedance analyzer (Agilent, Model 4294A). Based on the above conditions and measured values, the relative dielectric constant ε of the cured film was calculated according to equation (a). r asked for.

[0194] (3) Making the capacitor The capacitor shown in FIG. 15 was fabricated. Copper was vacuum-deposited to a thickness of 100 nm on a 50 μm-thick PET film (trade name "U48", manufactured by Toray Industries, Inc.) 500 by resistance heating, and a photoresist (trade name "LC140-10cP", manufactured by Rohm and Haas Co., Ltd.) was spin-coated (1000 rpm x 20 seconds) on top of the copper, and dried by heating at 100°C for 10 minutes. The fabricated photoresist film was pattern-exposed through a mask using a parallel light mask aligner (PLA-501F, manufactured by Canon Inc.), and then shower-developed for 60 seconds with ELM-D (trade name, manufactured by Mitsubishi Gas Chemical Co., Ltd.), a 2.38 mass% TMAH aqueous solution, using an automatic developing device (AD-2000, manufactured by Takizawa Sangyo Co., Ltd.), and then washed with water for 30 seconds. After that, it was etched for 2 minutes with Cu-03 (trade name, manufactured by Kanto Chemical Co., Ltd.), and then washed with water for 30 seconds. The resist was peeled off by immersing the film in JELK-101 (trade name, manufactured by Kanto Chemical Co., Ltd.) for 2 minutes, and then washed with water for 30 seconds, followed by drying by heating at 120°C for 20 minutes to form the lower electrode 51. Next, the resin composition of the present invention was spin-coated (800 rpm x 10 seconds) on the PET film on which the lower electrode 51 was formed, and then heat-treated at 110°C for 2 minutes, followed by heating at 150°C for 30 minutes using a drying oven to form a dielectric film 52 having a thickness of 400 nm. Next, the conductive paste of Preparation Example 2 was applied with a bar coater, and pre-baked at 100°C for 10 minutes in a drying oven. Thereafter, the film was exposed to light using an exposure device "PEM-8M", and then immersed and developed in a 0.5% Na2CO3 solution for 30 seconds, rinsed with ultrapure water, and cured in a drying oven at 140°C for 30 minutes to form the upper electrode 53.

[0195] (4) Fabrication of FET The FET shown in FIG. 16 was fabricated. Copper was vacuum-deposited to a thickness of 100 nm on a PET film (trade name "U48", manufactured by Toray Industries, Inc.) 600 with a thickness of 50 μm by resistance heating, and a photoresist (trade name "LC140-10cP", manufactured by Rohm and Haas Co., Ltd.) was spin-coated (1000 rpm x 20 seconds) on top of the copper, and dried by heating at 100°C for 10 minutes. The fabricated photoresist film was pattern-exposed through a mask using a parallel light mask aligner (PLA-501F, manufactured by Canon Inc.), and then shower-developed for 60 seconds with ELM-D (trade name, manufactured by Mitsubishi Gas Chemical Co., Ltd.), a 2.38 mass% TMAH aqueous solution, using an automatic developing device (AD-2000, manufactured by Takizawa Sangyo Co., Ltd.), and then washed with water for 30 seconds. The film was then etched for 2 minutes with Cu-03 (trade name, manufactured by Kanto Chemical Co., Ltd.), and then washed with water for 30 seconds. The resist was peeled off by immersing the film in JELK-101 (trade name, manufactured by Kanto Chemical Co., Ltd.) for 2 minutes, and then washed with water for 30 seconds, followed by drying by heating at 120°C for 20 minutes to form a gate electrode 61. Next, the resin composition of the present invention was spin-coated (800 rpm x 10 seconds) onto the PET film on which the gate electrode 61 was formed, and then heat-treated at 110°C for 2 minutes, followed by heat-treatment at 150°C for 30 minutes using a drying oven to form a gate insulating film 62 having a film thickness of 400 nm. Next, the semiconductor solution of Preparation Example 1 was ink-jet-coated onto the gate insulating film 62, and then heat-treated at 150°C for 30 minutes in the atmosphere to form a semiconductor layer 63. Next, the conductive paste of Preparation Example 2 was applied using a bar coater, and pre-baked in a drying oven at 100°C for 10 minutes. After that, the film was exposed to light using a “PEM-8M” exposure device, then developed by immersion in a 0.5% Na2CO3 solution for 30 seconds, rinsed with ultrapure water, and cured in a drying oven at 140°C for 30 minutes to form a source electrode 64 and a drain electrode 65.

[0196] (5) Making a rectifier circuit A rectifier circuit consisting of a FET 701 and a capacitor 702 shown in FIG. 17 was fabricated. Copper was vacuum-deposited to a thickness of 100 nm on a PET film (trade name "U48", manufactured by Toray Industries, Inc.) 700 with a thickness of 50 μm by a resistance heating method, and a photoresist (trade name "LC140-10cP", manufactured by Rohm and Haas Co., Ltd.) was spin-coated (1000 rpm x 20 seconds) thereon and dried by heating at 100° C. for 10 minutes. The fabricated photoresist film was pattern-exposed through a mask using a parallel light mask aligner (PLA-501F, manufactured by Canon Inc.), and then shower-developed for 60 seconds with ELM-D (trade name, manufactured by Mitsubishi Gas Chemical Co., Inc.), which is a 2.38 mass % TMAH aqueous solution, using an automatic developing device (AD-2000, manufactured by Takizawa Sangyo Co., Ltd.), and then washed with water for 30 seconds. Then, the film was etched with Cu-03 (trade name, manufactured by Kanto Chemical Co., Ltd.) for 2 minutes, and then washed with water for 30 seconds. The resist was peeled off by immersing the film in JELK-101 (trade name, manufactured by Kanto Chemical Co., Ltd.) for 2 minutes, washed with water for 30 seconds, and then heated and dried at 120°C for 20 minutes to form a gate electrode 71 of an FET element and a lower electrode 72 of a capacitor element. Next, the resin composition of the present invention was spin-coated (800 rpm x 10 seconds) on the PET film on which the gate electrode 71 and the lower electrode 72 were formed, and then heat-treated at 110°C for 2 minutes. After that, the film was exposed to light using an exposure device "PEM-8M", and then immersed and developed in a TMAH solution for 30 seconds, and rinsed with ultrapure water to form a hole pattern in the area where the via 79 was to be formed. After that, the film was heated at 150°C for 30 minutes using a drying oven to form an insulating film 73 having a thickness of 400 nm, which also serves as a gate insulating film of an FET element and a dielectric film of a capacitor element. Next, the semiconductor solution of Preparation Example 1 was inkjet coated on the insulating film 73, and heat-treated at 150°C for 30 minutes in the atmosphere to form a semiconductor layer 74. Next, the conductive paste of Preparation Example 2 was coated with a bar coater, and pre-baked in a drying oven at 100°C for 10 minutes. After that, it was exposed to light using an exposure device "PEM-8M", immersion developed in a 0.5% Na2CO3 solution for 30 seconds, rinsed with ultrapure water, and cured in a drying oven at 140°C for 30 minutes to form a source electrode 75 and a drain electrode 76 of the FET element, an upper electrode 77 of the capacitor element, wiring 78, and a via 79.

[0197] (6) Evaluation of short circuit rate of capacitor The interelectrode current (Ie) was measured for 100 capacitors fabricated with different applied voltages (Ve). The measurements were performed using a Semiconductor Characterization System 4200-SCS (Keithley Instruments, Inc.) in the atmosphere (temperature 20°C, humidity 35%). The electrode area was 1 mm 2 For the element, Ie at Ve=10V is 10 -8 Elements rated A or higher were considered short-circuited elements and were evaluated according to the following criteria. A (very good): Fewer than 1 out of 100 elements were shorted. B (Good): The number of elements with short circuits was between 2 and 5 out of 100. C (Acceptable): The number of elements with short circuits is between 5 and 10 out of 100. D (Fail): 10 or more short-circuited elements out of 100.

[0198] (7) Evaluation of FET leakage rate The source-drain current (Id)-source-drain voltage (Vsd) characteristics were measured for 100 fabricated FETs when the gate voltage (Vg) was changed. The measurements were performed using a Semiconductor Characterization System Model 4200-SCS (Keithley Instruments, Inc.) in the atmosphere (temperature 20°C, humidity 35%). The on-current was calculated from the drain current value at Vg = -20V. Furthermore, when the gate-source current (Vgs) at Vg = 20V was 10 -8 Elements rated A or higher were considered to be leak elements and were evaluated according to the following criteria. A (very good): The number of elements that leaked was 1 or less out of 100. B (Good): The number of elements showing leakage is between 2 and 5 out of 100. C (Acceptable): The number of elements showing leakage is between 5 and 10 out of 100. D (Fail): Leaks were observed in 10 or more elements out of 100.

[0199] (8) Yield evaluation of rectifier circuits In the 100 rectifier circuits thus produced, when an AC current was input to the source electrode 74, the DC current output to the drain electrode 75 was measured, and the yield of the rectifier circuits was evaluated according to the following criteria. A (very good): The number of non-operating circuits is 1 or less in 100. B (Good): The number of non-operating circuits is between 2 and 5 out of 100. C (Acceptable): The number of non-operating circuits is between 5 and 10 out of 100. D (Not acceptable): There are 10 or more non-operating circuits out of 100.

[0200] Synthesis Example 1: Synthesis of polysiloxane with inorganic particles (PS-01) A three-neck flask was charged with 10.90 g (0.08 mol) of methyltrimethoxysilane (MeSi), 5.25 g (0.02 mol) of 3-trimethoxysilylpropylsuccinic anhydride (SucSi), 24.84 g (0.10 mol) of 1-naphthyltrimethoxysilane (NapSi), 133.68 g of “Optraque (registered trademark)” TR-550 (manufactured by JGC Catalysts and Chemicals Co., Ltd.), which is a 20.6 mass% titanium oxide-silicon oxide composite particle methanol dispersion (particle content: 100 parts by mass relative to 100 parts by mass of the mass (27.54 g) when the organosilane is completely condensed), and 102.28 g of diacetone alcohol (DAA, boiling point 168°C). An aqueous phosphoric acid solution prepared by dissolving 0.205 g of phosphoric acid (0.50 mass% relative to the charged monomer) in 11.16 g of water was added over a period of 10 minutes while stirring at room temperature. After that, the flask was immersed in a 40°C oil bath and stirred for 60 minutes, and the oil bath was heated to 115°C over 30 minutes. One hour after the start of the temperature increase, the internal temperature of the solution reached 100°C, and it was heated and stirred for 2 hours from that point (internal temperature was 100-110°C). The resin solution obtained by heating and stirring was cooled in an ice bath, and then 2% by weight of anion exchange resin and cation exchange resin were added to the resin solution and stirred for 12 hours. After stirring, the anion exchange resin and cation exchange resin were removed by filtration to obtain a solution of polysiloxane (PS-01) to which inorganic particles were bonded. During the temperature increase and heating and stirring, nitrogen was flowed at 0.05 l (liter) / min. A total of 121.19 g of by-products, methanol and water, was distilled out during the reaction. The solid content concentration of the obtained solution PS-01 of polysiloxane to which inorganic particles were bonded was 33% by mass.

[0201] Synthesis Example 2: Synthesis of polysiloxane (PS-02) 10.90g (0.08mol) of methyltrimethoxysilane (MeSi), 5.25g (0.02mol) of 3-trimethoxysilylpropylsuccinic anhydride (SucSi), and 24.84g (0.10mol) of 1-naphthyltrimethoxysilane (NapSi) were dissolved in 64.26g of propylene glycol monobutyl ether (boiling point 170°C), and 11.16g of water and 0.205g of phosphoric acid were added thereto while stirring. The resulting solution was heated at a bath temperature of 105°C for 2 hours, and the internal temperature was raised to 70°C, and the components mainly consisting of by-product methanol were distilled out. Next, the solution was heated at a bath temperature of 130°C for 2.0 hours, and the internal temperature was raised to 110°C, and the components mainly consisting of water and propylene glycol monobutyl ether were distilled out. The resin solution obtained by heating and stirring was cooled in an ice bath, and then 2% by weight of anion exchange resin and cation exchange resin were added to the resin solution and stirred for 12 hours. After stirring, the anion exchange resin and cation exchange resin were removed by filtration to obtain a polysiloxane solution with a solid concentration of 36.0 wt%.

[0202] Synthesis Example 3: Synthesis of polysiloxane (PS-03) 61.29g (0.09 mol) of methyltrimethoxysilane, 12.31g (0.01 mol) of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 99.15g (0.10 mol) of phenyltrimethoxysilane were dissolved in 48.84g of propylene glycol monobutyl ether (boiling point 170°C), and 10.98g of water and 0.173g of phosphoric acid were added thereto while stirring. The resulting solution was heated at a bath temperature of 105°C for 2 hours, and the internal temperature was raised to 90°C, and a component mainly consisting of by-product methanol was distilled out. The solution was then heated at a bath temperature of 130°C for 2.0 hours, and the internal temperature was raised to 118°C, and a component mainly consisting of water and propylene glycol monobutyl ether was distilled out. The resin solution obtained by heating and stirring was cooled in an ice bath, and then anion exchange resin and cation exchange resin were added at 2% by weight each relative to the resin solution, and stirred for 12 hours. After stirring, the anion exchange resin and cation exchange resin were removed by filtration to obtain a polysiloxane solution with a solids concentration of 36.0 wt %.

[0203] Synthesis Example 4: Synthesis of naphthoquinone diazide compound (QD-01) Under a dry nitrogen stream, 15.32 g (0.05 mol) of Ph-cc-AP-MF (trade name, manufactured by Honshu Chemical Industry Co., Ltd.) and 37.62 g (0.14 mol) of 5-naphthoquinone diazide sulfonyl chloride were dissolved in 450 g of 1,4-dioxane and brought to room temperature. 15.58 g (0.154 mol) of triethylamine mixed with 50 g of 1,4-dioxane was added dropwise so that the temperature in the system did not exceed 35°C. After the addition, the mixture was stirred at 30°C for 2 hours. The triethylamine salt was filtered, and the filtrate was poured into water. The precipitate was then collected by filtration. The precipitate was dried in a vacuum dryer to obtain a quinone diazide compound (QD-01) having the following structure.

[0204] Synthesis Example 5: Compound P1 (Polymerizable component: polymer having a polymerizable unsaturated group) Copolymerization ratio (by weight): ethyl acrylate (hereinafter, "EA") / 2-ethylhexyl methacrylate (hereinafter, "2-EHMA") / styrene (hereinafter, "St") / glycidyl methacrylate (hereinafter, "GMA") / acrylic acid (hereinafter, "AA") = 20 / 40 / 20 / 5 / 15.

[0205] In a reaction vessel in a nitrogen atmosphere, 150 g of diethylene glycol monoethyl ether acetate (hereinafter, "DMEA") was charged, and the temperature was raised to 80°C using an oil bath. A mixture consisting of 20 g of EA, 40 g of 2-EHMA, 20 g of St, 15 g of AA, 0.8 g of 2,2'-azobisisobutyronitrile, and 10 g of DMEA was added dropwise over 1 hour. After the dropwise addition was completed, the polymerization reaction was carried out for another 6 hours. Then, 1 g of hydroquinone monomethyl ether was added to stop the polymerization reaction. Subsequently, a mixture consisting of 5 g of GMA, 1 g of triethylbenzylammonium chloride, and 10 g of DMEA was added dropwise over 0.5 hours. After the dropwise addition was completed, the addition reaction was carried out for another 2 hours. The obtained reaction solution was purified with methanol to remove unreacted impurities, and further dried in vacuum for 24 hours to obtain compound P1.

[0206] Synthesis Example 6: Compound P2 (Polymerizable component: polymer having a polymerizable unsaturated group) Copolymerization ratio (by weight): bifunctional epoxy acrylate monomer (Epoxy Ester 3002A; manufactured by Kyoeisha Chemical Co., Ltd.) / bifunctional epoxy acrylate monomer (Epoxy Ester 70PA; manufactured by Kyoeisha Chemical Co., Ltd.) / GMA / St / AA=20 / 40 / 5 / 20 / 15.

[0207] In a reaction vessel in a nitrogen atmosphere, 150g of DMEA was charged and heated to 80°C using an oil bath. A mixture consisting of 20g of epoxy ester 3002A, 40g of epoxy ester 70PA, 20g of St, 15g of AA, 0.8g of 2,2'-azobisisobutyronitrile and 10g of DMEA was added dropwise over 1 hour. After completion of the dropwise addition, the polymerization reaction was carried out for another 6 hours. Then, 1g of hydroquinone monomethyl ether was added to stop the polymerization reaction. Subsequently, a mixture consisting of 5g of GMA, 1g of triethylbenzylammonium chloride and 10g of DMEA was added dropwise over 0.5 hours. After completion of the dropwise addition, the addition reaction was carried out for another 2 hours. The obtained reaction solution was purified with methanol to remove unreacted impurities, and further dried in vacuum for 24 hours to obtain compound P2.

[0208] Synthesis Example 7: Compound P3, which is a urethane-modified compound of compound P2 (polymerizable component: polymer having a polymerizable unsaturated group) In a reaction vessel under a nitrogen atmosphere, 100 g of diethylene glycol monoethyl ether acetate (hereinafter, "DMEA") was charged, and the temperature was raised to 80°C using an oil bath. To this, a mixture consisting of 10 g of photosensitive component P2, 3.5 g of n-hexyl isocyanate, and 10 g of DMEA was added dropwise over 1 hour. After the dropwise addition was completed, the reaction was allowed to proceed for an additional 3 hours. The resulting reaction solution was purified with methanol to remove unreacted impurities, and further vacuum dried for 24 hours to obtain compound P3 having a urethane bond.

[0209] Preparation Example 1: Preparation of semiconductor solution 1.0 mg of CNT (CNI, single-walled CNT, purity 95%) was added to a 10 ml solution of 2.0 mg of poly(3-hexylthiophene) (P3HT) (Aldrich Corporation), and the mixture was subjected to ultrasonic stirring at 20% output for 4 hours using an ultrasonic homogenizer (Tokyo Rikakikai Co., Ltd., VCX-500) while cooling on ice, to obtain CNT dispersion A (CNT composite concentration relative to solvent: 0.96 g / l).

[0210] Next, a semiconductor solution for forming a semiconductor layer was prepared. The above CNT dispersion A was filtered using a membrane filter (pore size 10 μm, diameter 25 mm, Millipore Omnipore Membrane) to remove CNT composites with a length of 10 μm or more. 5 ml of o-dichlorobenzene (Wako Pure Chemical Industries, Ltd.) was added to the obtained filtrate, and then a rotary evaporator was used to distill off chloroform, which is a low boiling point solvent, and the solvent was replaced with o-dichlorobenzene to obtain CNT dispersion B. 3 mL of o-dichlorobenzene was added to 1 ml of CNT dispersion B to obtain a semiconductor solution (CNT composite concentration relative to the solvent: 0.03 g / l).

[0211] Preparation Example 2: Preparation of conductive paste In a 100 ml clean bottle, 1.6 g of compound P1, 0.4 g of compound P3, 0.4 g of photopolymerization initiator OXE-01 (manufactured by BASF Japan Ltd.), 0.06 g of acid generator SI-110 (manufactured by Sanshin Chemical Industry Co., Ltd.), and 38 g of diacetone alcohol (manufactured by Sankyo Chemical Co., Ltd.) were added and mixed with a rotation-revolution vacuum mixer "Awatori Rentaro" (registered trademark) (ARE-310; manufactured by Thinky Co., Ltd.) to obtain 40.86 g of photosensitive resin solution (solid content 4.0 wt%). 20.0 g of the obtained photosensitive resin solution was mixed with 5.0 g of Ag particles having a volume average particle diameter of 0.5 μm, and kneaded using a three-roller "EXAKT M-50" (trade name, manufactured by EXAKT Co., Ltd.) to obtain 25 g of conductive paste.

[0212] Example 1 16.36 g of a solution of polysiloxane bonded to inorganic particles (PS-01, polymer A), 0.60 g of Arastar 700 (manufactured by Arakawa Chemical Industries, Ltd., polymer B, styrene-maleic acid half ester copolymer) (mixture weight ratio of polymer A to polymer B is 90:10), 0.54 g of a quinone diazide compound (QD-01), 300 ppm of BYK-333 (polysiloxane surfactant, manufactured by BYK Japan Co., Ltd.), and 33.04 g of DAA were mixed and stirred under yellow light to obtain a homogeneous solution, which was then filtered through a 0.20 μm filter to obtain an insulating material solution (solid concentration 12 mass%).

[0213] The dielectric constant of the insulator was measured by the method described in (2) using the obtained insulator solution. In addition, a capacitor was fabricated by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). In addition, a FET was fabricated by the method described in (4), the thickness of the gate insulating film was evaluated by the method described in (1), and the FET characteristics were evaluated by the method described in (7). In addition, a rectifier circuit was fabricated by the method described in (5), the thickness of the insulating film was evaluated by the method described in (1), and the yield of the rectifier circuit was evaluated by the method described in (8). The results are shown in Tables 1 to 4.

[0214] Example 2 An insulating material solution (solid concentration 12% by mass) was obtained in the same manner as in Example 1, except that the amount of polysiloxane bonded to inorganic particles (PS-01) was changed to 13.64 g, the amount of Alastar 700 to 1.50 g, and the amount of DAA to 34.86 g (the mixing weight ratio of polymer A to polymer B was 75:25).

[0215] The obtained insulator solution was used to measure the relative dielectric constant of the insulator by the method described in (2). In addition, a capacitor was fabricated by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). The results are shown in Tables 1 and 2.

[0216] Example 3 An insulating material solution (solid concentration 12% by mass) was obtained in the same manner as in Example 1, except that the amount of the solution of polysiloxane bonded to inorganic particles (PS-01) was changed to 9.09 g, the amount of Alastar 700 to 3.00 g, and the amount of DAA to 37.91 g (the mixing weight ratio of polymer A and polymer B was 50:50).

[0217] The obtained insulator solution was used to measure the relative dielectric constant of the insulator by the method described in (2). In addition, a capacitor was fabricated by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). The results are shown in Tables 1 and 2.

[0218] Example 4 An insulating material solution (solid concentration 12% by mass) was obtained in the same manner as in Example 1, except that the amount of polysiloxane bonded to inorganic particles (PS-01) was changed to 17.27 g, the amount of Alastar 700 to 0.30 g, and the amount of DAA to 32.42 g (the mixing weight ratio of polymer A to polymer B was 95:5).

[0219] The obtained insulator solution was used to measure the relative dielectric constant of the insulator by the method described in (2). In addition, a capacitor was fabricated by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). The results are shown in Tables 1 and 2.

[0220] Example 5 An insulating material solution (solid concentration 12 mass%) was obtained in the same manner as in Example 1, except that 1.35 g of WR-301 (ADEKA Corporation, propylene glycol monomethyl ether acetate solution, 44.5 wt%, polyester having a carboxylic acid residue represented by general formula (5), polymer B) was used instead of Alastar 700 and the amount of DAA was changed to 32.29 g (the mixing weight ratio of polymer A to polymer B was 90:10).

[0221] Using the obtained insulator solution, the relative dielectric constant of the insulator was measured by the method described in (2). A capacitor was also prepared by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). A FET was also prepared by the method described in (4), the thickness of the gate insulating film was evaluated by the method described in (1), and the FET characteristics were evaluated by the method described in (7). A rectifier circuit was also prepared by the method described in (5), the thickness of the insulating film was evaluated by the method described in (1), and the yield of the rectifier circuit was evaluated by the method described in (8). The results are shown in Tables 1 to 4.

[0222] Example 6 An insulating material solution (solid concentration 12% by mass) was obtained in the same manner as in Example 5, except that the amount of the inorganic particle-bonded polysiloxane solution (PS-01) was changed to 13.64 g, the amount of WR-301 was changed to 3.37 g, and the amount of DAA was changed to 32.99 g (the mixing weight ratio of polymer A to polymer B was 75:25).

[0223] The obtained insulator solution was used to measure the relative dielectric constant of the insulator by the method described in (2). In addition, a capacitor was fabricated by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). The results are shown in Tables 1 and 2.

[0224] Example 7 An insulating material solution (solid concentration 12 mass%) was obtained in the same manner as in Example 5, except that the amount of the solution of polysiloxane bonded to inorganic particles (PS-01) was changed to 9.09 g, the amount of WR-301 was changed to 6.74 g, and the amount of DAA was changed to 34.17 g (the mixing weight ratio of polymer A and polymer B was 50:50).

[0225] The obtained insulator solution was used to measure the relative dielectric constant of the insulator by the method described in (2). In addition, a capacitor was fabricated by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). The results are shown in Tables 1 and 2.

[0226] Example 8 An insulating material solution (solid concentration 12 mass%) was obtained in the same manner as in Example 5, except that the amount of the inorganic particle-bonded polysiloxane solution (PS-01) was changed to 17.27 g, the amount of WR-301 was changed to 0.67 g, and the amount of DAA was changed to 32.05 g (the mixing weight ratio of polymer A to polymer B was 95:5).

[0227] The obtained insulator solution was used to measure the relative dielectric constant of the insulator by the method described in (2). In addition, a capacitor was fabricated by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). The results are shown in Tables 1 and 2.

[0228] Example 9 An insulating material solution (solid concentration 12% by mass) was obtained in the same manner as in Example 1, except that 1.67 g of the polysiloxane solution (PS-02, polymer B) synthesized in Synthesis Example 2 was used instead of Alastar 700, the amount of the polysiloxane solution bonded to inorganic particles (PS-01) was changed to 18.00 g, and the amount of DAA was changed to 30.33 g (the mixing weight ratio of polymer A to polymer B was 90:10).

[0229] Using the obtained insulator solution, the relative dielectric constant of the insulator was measured by the method described in (2). A capacitor was also prepared by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). A FET was also prepared by the method described in (4), the thickness of the gate insulating film was evaluated by the method described in (1), and the FET characteristics were evaluated by the method described in (7). A rectifier circuit was also prepared by the method described in (5), the thickness of the insulating film was evaluated by the method described in (1), and the yield of the rectifier circuit was evaluated by the method described in (8). The results are shown in Tables 1 to 4.

[0230] Example 10 An insulating material solution (solid concentration 12% by mass) was obtained in the same manner as in Example 9, except that the amount of the polysiloxane solution to which inorganic particles were bonded (PS-01) was changed to 13.64 g, the amount of the polysiloxane solution (PS-02) to 4.17 g, and the amount of DAA to 32.20 g were changed (the mixing weight ratio of polymer A to polymer B was 75:25).

[0231] The obtained insulator solution was used to measure the relative dielectric constant of the insulator by the method described in (2). In addition, a capacitor was fabricated by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). The results are shown in Tables 1 and 2.

[0232] Example 11 An insulating material solution (solid concentration 12 mass%) was obtained in the same manner as in Example 9, except that the amount of the polysiloxane solution bonded to inorganic particles (PS-01) was changed to 9.09 g, the amount of the polysiloxane solution (PS-02) was changed to 8.33 g, and the amount of DAA was changed to 32.58 g (the mixing weight ratio of polymer A and polymer B was 50:50).

[0233] The obtained insulator solution was used to measure the relative dielectric constant of the insulator by the method described in (2). In addition, a capacitor was fabricated by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). The results are shown in Tables 1 and 2.

[0234] Example 12 An insulating material solution (solid content concentration 12 mass%) was obtained in the same manner as in Example 9, except that the amount of the polysiloxane solution bonded to inorganic particles (PS-01) was changed to 17.27 g, the amount of the polysiloxane solution (PS-02) was changed to 0.83 g, and the amount of DAA was changed to 31.89 g (the mixing weight ratio of polymer A to polymer B was 95:5).

[0235] The obtained insulator solution was used to measure the relative dielectric constant of the insulator by the method described in (2). In addition, a capacitor was fabricated by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). The results are shown in Tables 1 and 2.

[0236] Example 13 An insulating solution (solid concentration 12% by mass) was obtained in the same manner as in Example 9 in the same manner as in Example 1, except that 1.67 g of the polysiloxane solution (PS-03, polymer B) synthesized in Synthesis Example 3 was used instead of Alastar 700, the amount of the polysiloxane solution bonded to inorganic particles (PS-01) was changed to 18.00 g, and the amount of DAA was changed to 30.33 g (the mixing weight ratio of polymer A to polymer B was 90:10).

[0237] Using the obtained insulator solution, the relative dielectric constant of the insulator was measured by the method described in (2). A capacitor was also prepared by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). A FET was also prepared by the method described in (4), the thickness of the gate insulating film was evaluated by the method described in (1), and the FET characteristics were evaluated by the method described in (7). A rectifier circuit was also prepared by the method described in (5), the thickness of the insulating film was evaluated by the method described in (1), and the yield of the rectifier circuit was evaluated by the method described in (8). The results are shown in Tables 1 to 4.

[0238] Example 14 An insulating material solution (solid concentration 12 mass%) was obtained in the same manner as in Example 13, except that the amount of the inorganic particle-bonded polysiloxane solution (PS-01) was changed to 13.64 g, the amount of the polysiloxane solution (PS-03) was changed to 4.17 g, and the amount of DAA was changed to 32.20 g (the mixture weight ratio of polymer A and polymer B was 75:25).

[0239] The obtained insulator solution was used to measure the relative dielectric constant of the insulator by the method described in (2). In addition, a capacitor was fabricated by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). The results are shown in Tables 1 and 2.

[0240] Example 15 An insulating material solution (solid concentration 12 mass%) was obtained in the same manner as in Example 9, except that the amount of the polysiloxane solution bonded to inorganic particles (PS-01) was changed to 9.09 g, the amount of the polysiloxane solution (PS-03) was changed to 8.33 g, and the amount of DAA was changed to 32.58 g (the mixing weight ratio of polymer A and polymer B was 50:50).

[0241] The obtained insulator solution was used to measure the relative dielectric constant of the insulator by the method described in (2). In addition, a capacitor was fabricated by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). The results are shown in Tables 1 and 2.

[0242] Example 16 An insulating material solution (solid content concentration 12 mass%) was obtained in the same manner as in Example 9, except that the amount of the polysiloxane solution bonded to inorganic particles (PS-01) was changed to 17.27 g, the amount of the polysiloxane solution (PS-03) was changed to 0.83 g, and the amount of DAA was changed to 31.89 g (the mixing weight ratio of polymer A to polymer B was 95:5).

[0243] The obtained insulator solution was used to measure the relative dielectric constant of the insulator by the method described in (2). In addition, a capacitor was fabricated by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). The results are shown in Tables 1 and 2.

[0244] Example 17 An insulating material solution (solid concentration: 12 mass %) was obtained in the same manner as in Example 2, except that the surfactant BYK333 (300 ppm) was changed to DFX-18 (150 ppm) (mixture weight ratio of polymer A and polymer B was 75:25).

[0245] The obtained insulator solution was used to measure the relative dielectric constant of the insulator by the method described in (2). In addition, a capacitor was fabricated by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). The results are shown in Tables 1 and 2.

[0246] Example 18 An insulating material solution (solid concentration: 12 mass %) was obtained in the same manner as in Example 6, except that the surfactant BYK333 (300 ppm) was changed to DFX-18 (150 ppm) (mixture weight ratio of polymer A and polymer B was 75:25).

[0247] The obtained insulator solution was used to measure the relative dielectric constant of the insulator by the method described in (2). In addition, a capacitor was fabricated by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). The results are shown in Tables 1 and 2.

[0248] Example 19 An insulating material solution (solid concentration: 12 mass %) was obtained in the same manner as in Example 10, except that the surfactant BYK333 (300 ppm) was changed to DFX-18 (150 ppm) (mixture weight ratio of polymer A and polymer B was 75:25).

[0249] Using the obtained insulator solution, the relative dielectric constant of the insulator was measured by the method described in (2). A capacitor was also prepared by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). A FET was also prepared by the method described in (4), the thickness of the gate insulating film was evaluated by the method described in (1), and the FET characteristics were evaluated by the method described in (7). A rectifier circuit was also prepared by the method described in (5), the thickness of the insulating film was evaluated by the method described in (1), and the yield of the rectifier circuit was evaluated by the method described in (8). The results are shown in Tables 1 to 4.

[0250] Example 20 An insulating material solution (solid concentration: 12 mass %) was obtained in the same manner as in Example 14, except that the surfactant BYK333 (300 ppm) was changed to DFX-18 (150 ppm) (mixture weight ratio of polymer A and polymer B was 75:25).

[0251] The obtained insulator solution was used to measure the relative dielectric constant of the insulator by the method described in (2). In addition, a capacitor was fabricated by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). The results are shown in Tables 1 and 2.

[0252] Comparative Example 1 18.18 g of a solution of polysiloxane bonded to inorganic particles (PS-01), 0.54 g of a quinone diazide compound (QD-01), 300 ppm of BYK-333 (a polysiloxane surfactant, manufactured by BYK Japan Co., Ltd.), and 31.82 g of DAA were mixed and stirred under a yellow light to obtain a homogeneous solution, which was then filtered through a 0.20 μm filter to obtain an insulating material solution (solid concentration 12 mass%).

[0253] Using the obtained insulator solution, the relative dielectric constant of the insulator was measured by the method described in (2). A capacitor was also prepared by the method described in (3), the thickness of the dielectric film was evaluated by the method described in (1), and the short circuit rate was evaluated by the method described in (6). A FET was also prepared by the method described in (4), the thickness of the gate insulating film was evaluated by the method described in (1), and the FET characteristics were evaluated by the method described in (7). A rectifier circuit was also prepared by the method described in (5), the thickness of the insulating film was evaluated by the method described in (1), and the yield of the rectifier circuit was evaluated by the method described in (8). The results are shown in Tables 1 to 4.

[0254] Comparative Example 2: Preparation of Insulator Solution An insulator solution was prepared in the same manner as in Example 1, except that polystyrene (manufactured by SigmaAldrich) was used instead of Alastar 700. However, titanium oxide particles precipitated, and a homogeneous solution could not be obtained.

[0255] [Table 1]

[0256] [Table 2]

[0257] [Table 3]

[0258] [Table 4] [Explanation of symbols]

[0259] 11, 31, 61, 71 Gate electrode 12, 62 Gate insulating film 13, 35, 64, 75 Source electrode 14, 34, 63, 74 Semiconductor layer 15, 36, 65, 76 Drain electrode 38, 78 Wiring 39, 79 Via 100, 200, 300, 400, 500, 600, 700 Insulating substrate 301, 701 FET elements 302, 702 Capacitor element 21, 32, 51, 72 Lower electrode 22, 52 Dielectric film 23, 37, 53, 77 upper electrode 33, 33A, 33B, 73 Insulating film 40 Antenna 41 Demodulation circuit 42 Control circuit 43 Modulation Circuit 44 Memory circuit 45 Power generation section

Claims

1. at least, (a) Polymer A: A polymer in which a polymer is covalently bonded to inorganic particles having hydroxyl groups on the surface thereof, (b) Polymer B: a polymer that is not covalently bonded to the inorganic particles and has a functional group capable of forming a hydrogen bond with a hydroxy group on the surface of the inorganic particles contained in the polymer A; and (c) Solvent Contains The polymer contained in the polymer A contains a polysiloxane, and the polysiloxane has a structural unit represented by general formula (1), the polymer contained in the polymer B includes at least one selected from the group consisting of polysiloxane, polyamide, polyamideimide, polyimide, polybenzimidazole, polyvinyl alcohol, polyhydroxystyrene, polyacetal, polycarbonate, polyarylate, polyphenylene sulfide, polyethersulfone, polyetherketone, polyphthalamide, polyethernitrile, polymethyl methacrylate, polymethacrylamide, aromatic polyether, novolac resin, phenol resin, acrylic resin, epoxy resin, melamine resin, and urea resin; the inorganic particles include at least one selected from the group consisting of tin oxide-titanium oxide composite particles, silicon oxide-titanium oxide composite particles, titanium oxide particles, zirconium oxide particles, hafnium oxide particles, yttrium oxide particles, niobium oxide particles, tantalum oxide particles, tin oxide particles, tin oxide-zirconium oxide composite particles, silicon oxide-zirconium oxide composite particles, aluminum oxide particles, barium titanate particles, strontium titanate particles, barium titanate-strontium titanate composite particles, lead zirconate titanate particles, lead lanthanum zirconate titanate particles, strontium bismuth niobate particles, strontium bismuth titanate niobate particles, and strontium bismuth tantalate particles, Resin composition. 【Chemistry 1】 (In the general formula (1), R 1 R represents a hydrogen atom, an alkyl group, a cycloalkyl group, a heterocyclic group, an aryl group, a heteroaryl group, or an alkenyl group. 2 represents a hydrogen atom, an alkyl group, a cycloalkyl group, or a silyl group; m represents 0 or 1. 1 represents an organic group containing at least two of a carboxyl group, a sulfo group, a thiol group, a phenolic hydroxyl group, or a derivative thereof. However, when the derivative is a cyclic condensation structure of two of the carboxyl group, the sulfo group, the thiol group, and the phenolic hydroxyl group, A 1 represents an organic group having at least one cyclic condensed structure.

2. The resin composition according to claim 1 , wherein the inorganic particles contained in the polymer A are inorganic oxide particles.

3. 3. The resin composition according to claim 1, wherein the polymer B has at least one functional group selected from the group consisting of a carboxyl group, a sulfo group, a phosphate group, a mercapto group, a hydroxyl group, an epoxy group, and derivatives thereof.

4. The resin composition according to any one of claims 1 to 3, wherein the polymer B comprises at least one selected from the group consisting of a polysiloxane having a structural unit represented by general formula (4), a resin having a phenolic hydroxyl group, a polyester having a carboxylic acid residue represented by general formula (5), and polymaleic acid and a derivative thereof. 【Chemistry 2】 (In the general formula (4), R 5 R represents a hydrogen atom, an alkyl group, a cycloalkyl group, a heterocyclic group, an aryl group, a heteroaryl group, or an alkenyl group. 6 represents a hydrogen atom, an alkyl group, a cycloalkyl group, or a silyl group; n represents 0 or 1. 2 represents an organic group containing at least one of a carboxyl group, a sulfo group, a thiol group, a phenolic hydroxyl group, an epoxy group, or a derivative thereof. However, when the derivative is a cyclic condensation structure of any two of the carboxyl group, the sulfo group, the thiol group, and the phenolic hydroxyl group, A 2 represents an organic group having at least one cyclic condensed structure. 【Chemistry 3】 (In the general formula (5), R 7 represents a hydrogen atom, an alkyl group, a cycloalkyl group, a heterocyclic group, an aryl group, a heteroaryl group, an alkenyl group, or an organic group represented by general formula (6). 【Chemistry 4】 (In the general formula (6), R 8 represents a hydroxyl group, an alkoxy group, or a functional group represented by general formula (7). 【Chemistry 5】 (In the general formula (7), R 9 R represents a functional group represented by an alkylene group or an oxyalkylene group. 10 represents a hydrogen atom or a methyl group.

5. The resin composition according to any one of claims 1 to 4, wherein the content of (b) polymer B is 8 parts by weight or more and 60 parts by weight or less per 100 parts by weight of the total of (a) polymer A and (b) polymer B.

6. The resin composition according to any one of claims 1 to 5, further comprising a fluorine-based surfactant.

7. A method for manufacturing an element, comprising the following steps 1 to 3. (Step 1) A step of forming a conductive pattern that will become a lower electrode on a substrate (Step 2) A step of applying the resin composition according to any one of claims 1 to 6 onto the substrate on which the conductive pattern is formed and drying the composition to obtain a coating film. (Step 3) A step of forming a conductive pattern that will become an upper electrode on the coating film.

8. A method for manufacturing an element, comprising the following steps 1' to 3'. (Step 1') A step of forming a conductive pattern that will become a lower electrode on a substrate (Step 2') A photosensitive resin composition containing the resin composition according to any one of claims 1 to 6 and a photosensitive organic component is applied to the substrate on which the conductive pattern is formed, and then dried to obtain a coating film. The coating film is then irradiated with actinic rays through a photomask and developed to form a dielectric pattern having an opening on the conductive pattern. (Step 3') A step of forming a conductive pattern that will become an upper electrode on the dielectric pattern.

9. The method for manufacturing an element according to claim 7 or 8, wherein the element is a capacitor.

10. The method for manufacturing an element according to claim 7 or 8, wherein the element is a field effect transistor.

11. The method for producing an element according to claim 10, further comprising the step of applying a semiconductor solution containing carbon nanotubes onto the coating film and drying the solution to obtain a semiconductor film.

Citation Information

Patent Citations

  • Titanium dioxide aqueous dispersion

    JP1995247119A

  • Water-in-oil type emulsion cosmetic

    JP1997301822A

  • Water-in-oil type emulsion cosmetic

    JP2004018415A

  • Field effect transistor

    JP2013115162A

  • Photosensitive resin composition and method for producing semiconductor element

    JP2017097378A